Porous film, organic optoelectronic device, and method for manufacturing porous film
The integration of a porous organic semiconductor film with a lower refractive index into organic electroluminescence devices addresses the issue of low external quantum efficiency and color purity, enhancing light extraction and maintaining high color fidelity for display applications.
Patent Information
- Application Number
- JP2021553519
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-25
- Filing Date
- 2020-10-22
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-10-22
AI Technical Summary
Existing organic electroluminescence (EL) devices suffer from low external quantum efficiency due to internal reflection at the interfaces between layers with different refractive indices, and the use of porous membranes above electrodes leads to mixed light wavelengths and decreased color purity, making them unsuitable for display applications.
A porous film made of an organic semiconductor with a lower refractive index than the organic semiconductor material, featuring continuous holes extending in the film thickness direction, is developed. This film is integrated into an organic photoelectronic device and manufactured using a method involving co-evaporation of a fluoropolymer and an organic semiconductor, followed by removal of the fluoropolymer to create the porous structure.
The porous film enhances the external quantum efficiency of organic EL devices by reducing internal reflection and improving light extraction, while maintaining high color purity, making the technology more suitable for display applications.
Smart Images

Figure 0007662159000015 
Figure 0007662159000016 
Figure 0007662159000017
Abstract
Description
[Technical field]
[0001] The present invention relates to a porous film, an organic optoelectronic device, and a method for producing a porous film. [Background technology]
[0002] Conventionally, organic photoelectron elements (organic electroluminescence elements, hereinafter referred to as organic EL elements) have been known as self-luminous elements. The basic structure of an organic EL element is that multiple layers, such as a light-emitting layer, an electron transport layer, and a hole transport layer, are laminated between a pair of electrodes.
[0003] In organic EL elements, electrons and holes supplied from a power source recombine in the internal light-emitting layer to generate photons and emit light. In the field of organic EL elements, many years of research and development have led to the achievement of an internal quantum efficiency of nearly 100%, which is the ratio of photons generated inside the element to the number of injected electrons.
[0004] Meanwhile, even in recent organic EL elements, the "external quantum efficiency," which is the ratio of "photons extracted outside the element" to "the number of injected electrons," remains at around 20-30%, and improvement is required.
[0005] One of the reasons for the low external quantum efficiency is thought to be internal reflection caused by the difference in refractive index between the layers constituting the organic EL element. As mentioned above, the organic EL element has several layers in addition to the light-emitting layer. These layers have different refractive indexes. Therefore, it is thought that the light generated in the light-emitting layer is reflected at the interface between the layers with different refractive indexes and is attenuated or absorbed inside the element before being emitted outside the element.
[0006] In response to this, a light emitting device is known in which a porous film is disposed above an anode or a cathode (see Patent Document 1). In the light emitting device described in Patent Document 1, it is expected that the light extraction efficiency will be improved by light scattering by the porous film. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Special Publication No. 2014-508385 Summary of the Invention [Problem to be solved by the invention]
[0008] However, in order to meet market demands for low power consumption and long life of elements, the higher the external quantum efficiency of an organic EL element, the more preferable it is. In this respect, there is room for improvement in the external quantum efficiency of the light-emitting device described in Patent Document 1. In addition, the light extracted by the light-emitting device described in Patent Document 1 is prone to mixing of light of various wavelengths due to light scattering, and the color purity is prone to decrease. Therefore, the light-emitting device described in Patent Document 1 has a problem in that it is difficult to apply it to a display.
[0009] The present invention has been made in view of the above circumstances, and aims to provide a porous film made of an organic semiconductor and having a lower refractive index than the organic semiconductor. Another aim is to provide an organic optoelectronic device having such a porous film. Another aim is to provide a method for producing such a porous film, which can easily produce such a porous film. [Means for solving the problem]
[0010] In order to solve the above problems, the present invention includes the following aspects.
[0011] [1] A porous film made of an organic semiconductor and having a plurality of continuous pores extending in the film thickness direction. [2] The porous film according to [1], wherein the organic semiconductor has a molecular weight of 300 to 1,000. [3] The porous film according to [1] or [2], wherein the interplanar spacing d value obtained by X-ray scattering is 5 to 100 nm. [4] The porous membrane according to any one of [1] to [3], having a porosity of 20 to 80 volume %. [5] The porous film according to any one of [1] to [4], further comprising a dopant for the organic semiconductor.
[0012] [6] An organic optoelectronic device comprising: a substrate; an anode provided on the substrate; a cathode facing the anode; an active layer disposed between the anode and the cathode; a hole transport layer disposed between the active layer and the anode; and an electron transport layer disposed between the active layer and the cathode, wherein at least one layer selected from the group consisting of the active layer, the hole transport layer, and the electron transport layer is the porous film according to any one of [1] to [5].
[0013] [7] A method for producing a porous film, comprising: a vapor deposition step of co-depositing a fluorine-containing polymer and an organic semiconductor soluble in a fluorine-containing solvent to form a film; and a removal step of removing the fluorine-containing polymer contained in the film, wherein in the vapor deposition step, a ratio of the fluorine-containing polymer to a total of the fluorine-containing polymer and the organic semiconductor is 20 to 80 volume %, and in the removal step, a fluorine-containing solvent that dissolves the fluorine-containing polymer but does not substantially dissolve the organic semiconductor is used to dissolve the fluorine-containing polymer contained in the film in the fluorine-containing solvent and remove the fluorine-containing polymer, thereby forming a plurality of continuous pores extending in the thickness direction of the film.
[0014] [8] The method for producing a porous film according to [7], wherein the organic semiconductor has a molecular weight of 300 to 1,000. [9] The method for producing a porous film according to [7] or [8], wherein in the vapor deposition step, a dopant for the organic semiconductor is co-deposited together with the fluorine-containing polymer and the organic semiconductor.
[10] The method for producing a porous membrane according to any one of [7] to [9], wherein the fluoropolymer has a weight average molecular weight of 1,500 to 50,000.
[11] The method for producing a porous membrane according to any one of [7] to
[10] , wherein the threshold temperature of the fluoropolymer determined under the following conditions is 340° C. or lower. (Measurement conditions) Fluorine-containing polymer 1×10 -3When heated at a vacuum of 10 Pa at a rate of 2°C per minute, the evaporation rate is 0.1 g / (m 2 sec) to 0.1g / (m 2 The boundary temperature where the temperature is equal to or higher than the threshold temperature (seconds).
[0015]
[12] The method for producing a porous membrane according to any one of [7] to
[11] , wherein the fluorine-containing polymer is a perfluoropolymer having an aliphatic ring structure in the main chain.
[13] The method for producing a porous membrane according to any one of [7] to
[11] , wherein the fluorine-containing polymer is a polymer having no aliphatic ring structure in its main chain and having a perfluoroalkyl group in its side chain.
[14] The fluorine-containing solvent's fluorinophilicity parameter P is determined by the following method: F The method for producing a porous membrane according to any one of [7] to
[13] , wherein is 1 or more. (Fluorophilic parameter P F ) 30 μL of the fluorine-containing solvent is dropped into a two-phase system of 3 g of toluene and 3 g of perfluoromethylcyclohexane, mixed, and allowed to stand overnight, and then the fluorine-containing solvent contained in the toluene and the fluorine-containing solvent contained in the perfluoromethylcyclohexane are measured by gas chromatography. The concentration (unit: mL / L) of the fluorine-containing solvent in the toluene is expressed as M P The concentration of the fluorine-containing solvent in the perfluoromethylcyclohexane (unit: mL / L) is M F When the above formula is used, the fluorine-philic parameter P is calculated by the following formula (A). F Let us assume that. P F =M F / M P …(A)
[0016]
[15] The method for producing a porous membrane according to any one of [7] to
[14] , wherein in the removing step, the membrane is immersed in the fluorine-containing solvent.
[16] The method for producing a porous membrane according to any one of [7] to
[14] , wherein in the removing step, the membrane is exposed to vapor of the fluorine-containing solvent.
[17] The method for producing a porous film according to any one of [7] to
[16] , wherein a plurality of the organic semiconductors are used, in the vapor deposition step, the fluorine-containing polymer and a first organic semiconductor are co-deposited to form a first film, and then the fluorine-containing polymer and a second organic semiconductor are co-deposited to form a second film, and in the removal step, the fluorine-containing polymer contained in the first film and the fluorine-containing polymer contained in the second film are removed.
[18] The method for producing a porous membrane according to any one of [7] to
[17] , further comprising, after the removing step, a step of depositing the organic semiconductor to close openings of the plurality of continuous pores. Effect of the Invention
[0017] According to the present invention, it is possible to provide a nanoporous film using an organic semiconductor as a forming material and having a lower refractive index than an organic semiconductor. It is also possible to provide an organic optoelectronic device having such a nanoporous film. It is also possible to provide a method for producing a nanoporous film that can easily produce such a nanoporous film. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a schematic perspective view showing a porous membrane of the first embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a scattering pattern in GI-SAXS. [Diagram 3] FIG. 3 is an electron microscope photograph showing an example of the porous membrane of the first embodiment. [Figure 4] FIG. 4 is a schematic diagram showing the steps of producing the porous membrane 1. As shown in FIG. [Diagram 5] FIG. 5 is a schematic diagram showing the steps of producing the porous membrane 1. As shown in FIG. [Figure 6] FIG. 6 is a schematic diagram showing the steps of producing the porous membrane 1. As shown in FIG. [Figure 7] FIG. 7 is a schematic diagram showing the steps of producing the porous membrane 1. As shown in FIG. [Figure 8] FIG. 8 is an explanatory diagram of a method for producing the porous membrane 2 according to the second embodiment. [Figure 9]FIG. 9 is an explanatory diagram of a method for producing the porous membrane 2 according to the second embodiment. [Figure 10] FIG. 10 is an explanatory diagram of a method for producing the porous membrane 2 according to the second embodiment. [Figure 11] FIG. 11 is an explanatory diagram of a manufacturing method of the porous membrane 3 according to the third embodiment. [Figure 12] FIG. 12 is an explanatory diagram of a manufacturing method of the porous membrane 3 according to the third embodiment. [Figure 13] FIG. 13 is a cross-sectional view illustrating an organic optoelectronic device (organic EL device) 100 according to a fourth embodiment. [Figure 14] FIG. 14 is an explanatory diagram of an organic EL element 200 according to the fifth embodiment. [Figure 15] FIG. 15 is a cross-sectional TEM photograph of the co-deposited film produced in Example 1-2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The terms used in the present invention have the following meanings. A "unit" constituting a polymer means a portion derived from one monomer molecule that exists in the polymer and constitutes the polymer. A unit resulting from addition polymerization of a monomer having a carbon-carbon unsaturated double bond is a divalent unit resulting from the cleavage of the unsaturated double bond. In addition, a unit obtained by chemically converting the structure of a certain unit after the formation of a polymer is also called a unit. Hereinafter, units derived from individual monomers may be referred to by the name of the monomer with "unit" added. The term "reactive functional group" means a group having reactivity that can form a bond by reacting (excluding radical reactions) between molecules of the fluoropolymer or with other components blended together with the fluoropolymer when heated, etc. The term "aliphatic ring" refers to a ring structure that does not exhibit aromaticity. The aliphatic ring may be saturated or unsaturated. The aliphatic ring refers to a carbon ring structure whose ring skeleton is composed only of carbon atoms, as well as a heterocyclic ring structure whose ring skeleton contains an atom (heteroatom) other than carbon atoms. Examples of the heteroatom include an oxygen atom, a nitrogen atom, and a sulfur atom.
[0020] The "external quantum efficiency" is a value expressed by the following formula. η EQE = γ × η S ×q×η out η EQE : external quantum efficiency (%), γ: charge balance, η S : Probability of luminescent exciton formation (%), q: Luminescence quantum yield (%), η out : Light extraction efficiency (%). The "refractive index of the fluorine-containing polymer" is a value measured in accordance with JIS K 7142.
[0021] [First embodiment] Hereinafter, the porous membrane and the manufacturing method of the porous membrane according to the present embodiment will be described with reference to Fig. 1 to Fig. 7. In addition, in all the following drawings, the dimensions and ratios of each component are appropriately changed in order to make the drawings easier to see.
[0022] Fig. 1 is a schematic perspective view showing a porous membrane of the present embodiment. As shown in Fig. 1, the porous membrane 1 of the present embodiment is made of an organic semiconductor and has a plurality of continuous pores 11 that are continuous in the film thickness direction. Such a porous membrane 1 has a lower refractive index than a film of an organic semiconductor that does not have the continuous pores 11. Furthermore, since the porous film 1 has a solid portion that is continuous in the film thickness direction, the film has continuous pores 11 and yet can ensure electrical conductivity. In addition, since the porous membrane 1 has continuous pores 11 formed in the film thickness direction, the conductivity is not the same in the planar direction and in the film thickness direction, and it is considered that the conductivity is anisotropic.
[0023] The refractive indexes of the "porous film 1" and the "organic semiconductor film having no continuous pores 11" can be measured using model samples formed on silicon substrates.
[0024] Specifically, the refractive index of the porous film 1 is measured using a multi-angle spectroscopic ellipsometry (M-2000U manufactured by J.A. Woollam Co.) by changing the angle of incidence of light in increments of 5 degrees from 45 to 75 degrees on a film formed on a silicon substrate. At each angle, the ellipsometry parameters Ψ and Δ are measured at approximately 1.6 nm intervals in the wavelength range of 450 to 800 nm. Using the obtained measurement data, a fitting analysis is performed on the dielectric function of the organic semiconductor using the Cauchy model, and the refractive index of the film formed on the silicon substrate for light with a wavelength of 600 nm can be obtained.
[0025] Any known organic semiconductor can be used, and an appropriate material can be selected depending on the function of the device including the porous membrane 1 of this embodiment. For example, examples of organic semiconductors include a hole injection material constituting a hole injection layer of an organic EL element, an electron injection material constituting an electron injection layer, a hole transport material constituting a hole transport layer, an electron transport material constituting an electron transport layer, and a host material or guest material constituting a light emitting layer.
[0026] Suitable examples of hole injection materials include aromatic amine derivatives, such as, but not limited to, α-NPD, TAPC, PDA, TPD, and m-MTDATA.
[0027] [ka]
[0028] Other examples of hole injection materials include the following materials. Semiconductor materials made of metal oxides such as molybdenum oxide or tungsten oxide Copper phthalocyanine and other organometallic complex materials Arylamine materials such as N,N'-diphenyl-N,N'-bis-[4-(phenyl-m-tolyl-amino)-phenyl]-biphenyl-4,4'-diamine (DNTPD), N,N'-di(1-naphthyl)-N,N'-diphenylbenzidine (NPB), 4,4',4"-tris(N,N-diphenylamino)triphenylamine (TDATA), dipyrazino[2,3-f:2',3'-h]quinoxaline-2,3,6,7,10,11-hexacarbonitrile (HAT-CN), 9,9',9"-triphenyl-9H,9'H,9"H-3,3':6',3"-tert-carbazole (Tris-PCz), 4,4',4"-tris(N,N-2-naphthylphenylamino)triphenylamine (2-TNATA) Polymeric semiconducting materials such as polyaniline / dodecylbenzenesulfonic acid (PANI / DBSA), poly(3,4-ethylenedioxythiophene) / poly(4-styrenesulfonate) (PEDOT / PSS), polyaniline camphorsulfonic acid (PANI / CSA), or polyaniline / poly(4-styrenesulfonate) (PANI / PSS) Commercially available products such as N-(diphenyl-4-yl)-9,9-dimethyl-N-(4-(9-phenyl-9H-carbazoyl-3-yl)phenyl)-9H-fluoren-2-amine (hereinafter referred to as "HT211"), HTM081 (manufactured by Merck), HTM163 (manufactured by Merck), HTM222 (manufactured by Merck), NHT-5 (manufactured by NoValed), NHT-18 (manufactured by NoValed), NHT-49 (manufactured by NoValed), NHT-51 (manufactured by NoValed), NDP-2 (manufactured by NoValed), and NDP-9 (manufactured by NoValed)
[0029] The hole injection materials exemplified above are commercially available. These hole injection materials may be commercially available or may be synthetic products. The hole injection materials may be used alone or in combination of two or more.
[0030] Known materials can be used as the electron injection material. Specific examples include inorganic compounds such as LiF, Cs2CO3, and CsF, as well as the following Alq3, PBD, TAZ, BND, OXD-7, and 8-hydroxyquinolinolato-lithium (Liq), but are not limited thereto. In addition, commercially available products such as NDN-1 (manufactured by NoValed) and NDN-26 (manufactured by NoValed) can be used.
[0031] [ka]
[0032] Examples of the material for the hole transport layer (hole transport material) include, but are not limited to, the aromatic amine derivatives such as α-NPD, PDA, TAPC, TPD, and m-MTDATA.
[0033] Other hole transport materials include triazole derivatives, oxadiazole derivatives, imidazole derivatives, pyrazoline derivatives and pyrazolone derivatives, phenylenediamine derivatives, arylamine derivatives, amino-substituted chalcone derivatives, oxazole derivatives, styrylanthracene derivatives, fluorenone derivatives, hydrazone derivatives, stilbene derivatives, silazane derivatives, etc. Among these, it is preferable to use porphyrin compounds, aromatic tertiary amine compounds and styrylamine compounds, in particular aromatic tertiary amine compounds.
[0034] Other examples of the hole transport material include the following materials. The arylamine materials such as DNTPD, NPB, TDATA, HAT-CN, 2-TNATA, Tris-PCz, 4,4',4"-tri(9-carbazoyl)triphenylamine (TCTA), 2,2',7,7'-tetrakis(N,N-diphenylamino)-2,7-diamino-9,9'-spirobifluorene (Spiro-TAD), and 2,2',7,7'-tetrakis(N,N-di-p-methoxyphenylamino)-9,9'-spirobifluorene (Spiro-MeOTAD) The polymer semiconductor materials such as PANI / DBSA, PEDOT / PSS, PANI / CSA, PANI / PSS, etc. The above-mentioned commercially available products, such as HT211, HTM081 (manufactured by Merck), HTM163 (manufactured by Merck), HTM222 (manufactured by Merck), NHT-5 (manufactured by NoValed), NHT-18 (manufactured by NoValed), NHT-49 (manufactured by NoValed), NHT-51 (manufactured by NoValed), NDP-2 (manufactured by NoValed), and NDP-9 (manufactured by NoValed)
[0035] These hole transport materials may be commercially available products or synthetic products. The hole transport materials may be used alone or in combination of two or more kinds.
[0036] A known material can be used as the material of the electron transport layer (electron transport material). For example, the electron transport material may be Alq3, PBD, TAZ, BND, OXD-7, 2,2',2''-(1,3,5-benzintriyl)-tris(1-phenyl-1-H-benzimidazole) (TPBi), 8-hydroxyquinolinolato-lithium (Liq), etc. Other examples of the electron transport material include BCP, t-Bu-PBD, and silole derivatives.
[0037] These electron transport materials may be commercially available products or synthetic products. The above electron transport materials may be used alone or in combination of two or more kinds.
[0038] The light-emitting layer may be formed from any of known materials, such as fluorescent materials, thermally activated delayed fluorescence (TADF) materials, and phosphorescent materials.
[0039] For example, materials for forming the light-emitting layer include, but are not limited to, light-emitting guest materials such as (E)-2-(2-(4-(dimethylamino)styryl)-6-methyl-4H-pyran-4-ylidene)malononitrile (DCM), 4-(dicyanomethylene)-2-methyl-6-julolidyl-9-enyl-4H-pyran (DCM2), Rubrene, Coumarin6, Ir(ppy)3, and (ppy)2Ir(acac); phosphorescent host materials such as 4,4'-bis(9H-carbazol-9-yl)biphenyl (CBP) and 3,3'-di(9H-carbazol-9-yl)-1,1'-biphenyl (mCBP); fluorescent host materials such as ADN and Alq3; and polymer materials such as polyphenylenevinylene (PPV) and MEH-PPV.
[0040] The material for forming the light-emitting layer may be used alone or in combination of two or more kinds. The material for forming the light-emitting layer is appropriately selected depending on the desired emission wavelength.
[0041] The organic semiconductor that is the material for forming the porous film 1 preferably has a molecular weight of 300 to 1000. The molecular weight of the organic semiconductor is more preferably 400 or more. Moreover, the molecular weight of the organic semiconductor is more preferably 900 or less.
[0042] If the molecular weight of the organic semiconductor is 300 or more, the glass transition temperature (Tg) of the organic semiconductor is high, and the heat resistance of the organic semiconductor film is improved. If the molecular weight is 1000 or less, the vapor pressure of the organic semiconductor is high, and it is possible to deposit the organic semiconductor at a temperature below the thermal decomposition temperature.
[0043] The upper limit and lower limit of the molecular weight of the organic semiconductor can be combined in any desired manner. That is, the molecular weight of the organic semiconductor may be 300-900, 400-1000, or 400-900.
[0044] The molecular weight of the organic semiconductor can be determined by measurement using Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS).
[0045] The porous film 1 is made of an organic semiconductor and is continuous in the film thickness direction. Therefore, the porous film 1 has a charge transport ability. The "charge" that the porous film 1 can transport refers to holes or electrons.
[0046] The continuous pores 11 are continuous in the thickness direction of the porous membrane 1. In Fig. 1, the continuous pores 11 penetrate the porous membrane 1 in the thickness direction.
[0047] The porosity of the porous film 1 is preferably 20 to 80% by volume. When the porosity of the porous film 1 is 20% by volume or more, the film has a sufficiently lower refractive index compared to an organic semiconductor film that does not have continuous pores 11. When the porosity of the porous film 1 is 80% by volume or less, the film strength of the porous film 1 can be sufficiently maintained. The porosity of the porous membrane 1 can be appropriately set within the above range depending on the desired refractive index of the porous membrane 1.
[0048] The porosity of the porous membrane 1 can be calculated from the following formula (B). In the following formula (B), the refractive index of air (n a ) is 1, and the refractive indexes of the organic semiconductor and the porous film are the values obtained by the measurement method described above. Porosity (%)=(n p -n o ) / (n a -n o ) × 100 …(B) n p : Refractive index of porous film n o : Refractive index of organic semiconductors n a : Refractive index of air
[0049] The interplanar spacing d value of the porous film 1 obtained by X-ray scattering is preferably 5 to 100 nm, and more preferably 5 to 60 nm. The above-mentioned d value corresponds to the distance between adjacent continuous pores 11. A larger d value indicates that adjacent continuous pores 11 are spaced farther apart, and a smaller d value indicates that adjacent continuous pores 11 are closer together. If the d value is within the above-mentioned range, visible light can be transmitted through the porous film 1 without being scattered.
[0050] The d value is a value obtained by evaluating the cluster structure by small angle X-ray scattering (SAXS). In detail, first, the Aichi Synchrotron BL8S3 is used as the incident X-ray, the wavelength is 1.5 Å (8.2 keV), the beam size is approximately 850 μm × 280 μm, the camera length is 1121.52 mm, the detector is R-AXISIV (imaging plate), and the exposure time is 60 seconds, and X-ray scattering diffraction is measured using the small-angle X-ray scattering method. The obtained data is circularly averaged using Fit 2D software to convert the two-dimensional data into one-dimensional data, and then background correction, transmittance correction, and air scattering correction are performed during IP reading to obtain the d value. Sample thickness correction is omitted due to its low accuracy and location unevenness. The conditions for measuring the d value are not limited to the above-mentioned method, and other measurement conditions may be used as long as the d value can be appropriately measured.
[0051] In the porous membrane 1, the plurality of continuous pores 11 are preferably formed toward the thickness direction of the porous membrane 1 (oriented in the thickness direction). In the following description, the property that the plurality of continuous pores 11 are formed in the thickness direction of the porous membrane 1 may be referred to as "vertical orientation."
[0052] The above-mentioned perpendicular orientation of the continuous pores 11 can be evaluated by grazing incidence small angle X-ray scattering (GI-SAXS). For example, the porous film 1 can be evaluated using BL-6A at the High Energy Accelerator Research Organization. The wavelength of the incident X-rays is 1.5 Å, the angle of incidence is 0.16° in the direction parallel to the surface of the porous film 1, the detector is PILATUS3 1M, and the camera length is 2.5 m. The measurement conditions are not limited to these, and any conditions that allow the orientation to be appropriately evaluated may be used.
[0053] In general, when a sample with a microstructure that is not oriented in a specific direction is irradiated with X-rays, the X-rays are scattered isotropically. On the other hand, when a sample with an oriented microstructure is irradiated with X-rays, the scattered X-rays have a regular scattering direction that reflects the orientation of the microstructure, and as a result of interference between the scattered lights, locally strong scattered light is observed.
[0054] FIG. 2 is a schematic diagram showing an example of a scattering pattern in GI-SAXS. In GI-SAXS, the direction of the orthogonal projection vector of the incident X-rays on the sample surface is defined as q x The direction parallel to the sample surface and perpendicular to the qx direction is called the q y direction, and the normal direction of the sample surface is q z The direction.
[0055] Figure 2 shows the q y q z This is an X-ray scattering pattern in a plane. FIG. 2(a) shows a model of the scattering pattern when a film (sample) having a microstructure or phase-separated structure oriented in the film thickness direction is evaluated by GI-SAXS. Figure 2(b) shows a model of the scattering pattern when a film (sample) having a microstructure or phase-separated structure oriented in a direction parallel to the film surface is evaluated by GI-SAXS. Figure 2(c) shows a model of the scattering pattern when a film (sample) with no orientation in the microstructure is evaluated by GI-SAXS. In Figure 2, q z The strongest signal rising in the direction corresponds to the X-rays that are specularly reflected from the sample surface. In the following explanation, the signal of "the X-rays that are specularly reflected from the sample surface" is referred to as "main signal X."
[0056] In this embodiment, as shown in FIG. 2(a), the scattering pattern is ±q y q at the position z When a strong signal a rising in the direction is detected, it is determined that the microstructure is oriented in the vertical direction. In addition, as shown in the scattering pattern in Fig. 2(b), the main signal X intersects with the main signal X, and the scattering patterns are ±q y When a signal b extending in the direction is detected, it is determined that the microstructures are oriented in a direction parallel to the membrane surface. Furthermore, when a signal c that overlaps with the main signal X and continues in a semicircular shape is detected, as in the scattering pattern shown in Figure 2(c), it is determined that the X-ray scattering is isotropic and there is no orientation in the microstructure. For detailed comparison, for each signal, q y Direction and q z It is advisable to compare the ratio of scattering intensities in different directions.
[0057] The diameter of the opening 11a of the continuous pores 11 is preferably 5 to 100 nm. If the diameter of the opening 11a of the continuous pores 11 is within this range, the diameter is sufficiently small relative to visible light, and therefore the visible light incident on the porous membrane 1 is not easily scattered.
[0058] The porous film 1 may further contain an organic semiconductor dopant. Any known dopant can be used, and an appropriate material can be selected depending on the function of the device including the porous film 1 of the present embodiment. By containing a dopant, the conductivity of the porous film 1 can be increased.
[0059] For example, the following materials can be mentioned as dopants for organic semiconductors used as hole injection materials. TCNQ, F4-TCNQ, PPDN, TCNNQ, F6-TCNNQ, HAT-CN, HATNA, HATNA-Cl6, HATNA-F6, C 60 F 36 , F 16Organic dopants such as CuPc, NDP-2 (Novaled), and NDP-9 (Novaled) Inorganic dopants such as MoO3, V2O5, WO3, ReO3, and CuI
[0060] Examples of dopants used as electron injection materials include 8-hydroxyquinolinolato-lithium (Liq), NDN-1 (manufactured by Novaled), and NDN-26 (manufactured by Novaled).
[0061] 3 is an electron microscope photograph showing an example of the porous membrane of this embodiment, which is an enlarged photograph of the surface of the porous membrane. As shown in the figure, the openings of a plurality of continuous pores 11 can be confirmed on the surface of the porous membrane 1. The continuous pores 11 of the porous membrane 1 shown in the figure have a diameter of about 10 to 20 nm.
[0062] 1 and 3, the continuous pores 11 are shown to penetrate the porous membrane 1, but this is not limiting. For example, the opening on one end of the continuous pores 11 may be blocked with the material for forming the porous membrane 1, or the openings on both ends of the continuous pores 11 may be blocked with the material for forming the porous membrane 1. The openings on one end or both ends of the continuous pores 11 may be crushed and blocked by physically or thermally treating the porous membrane 1, or may be blocked by further evaporating the material for forming the porous membrane 1 on the porous membrane 1. When at least one end of the continuous pores 11 is blocked with the material forming the porous membrane 1, the continuous pores 11 are considered to be formed continuously over a length that is 50% or more of the thickness of the porous membrane 1.
[0063] 4 to 7 are schematic diagrams showing the steps of manufacturing the porous membrane 1 described above. First, a substrate 50 on which a porous film 1 is to be formed is prepared, as shown in Fig. 4. Such a substrate 50 is placed in a chamber 500 of a vacuum deposition device, and an organic semiconductor 51a and a fluorine-containing polymer 52a are supplied from an organic semiconductor deposition source (crucible) 51 and a fluorine-containing polymer deposition source (crucible) 52, respectively, for co-deposition. Note that, although Fig. 4 shows that the organic semiconductor and the fluorine-containing polymer are deposited from separate deposition sources, they may be deposited from the same deposition source.
[0064] During co-deposition, deposition conditions are set so that the ratio of the fluorine-containing polymer to the total of the fluorine-containing polymer and the organic semiconductor in the co-deposition film formed on the substrate 50 is 20 to 80% by volume.
[0065] The organic semiconductor 51a used can be one that does not decompose when heated during deposition. Whether or not the organic semiconductor used does not decompose when heated during deposition can be determined by determining the weight loss rate by the following method.
[0066] (Judgment method) The measurement is performed using a vacuum differential thermobalance (Advance Riko Co., Ltd.: VPE-9000). 50 mg of the organic semiconductor is placed in a cell with an inner diameter of 7 mm, and the temperature is measured at 1 × 10 -3 ~1×10 -4 The weight loss rate (%) of the organic semiconductor was measured when the temperature was increased to 500°C at a rate of 2°C per minute under a vacuum of 100 Pa. The temperature at which the weight loss rate reached 50% (T d50 ) is required. Next, the weight loss rate of the organic semiconductor was measured using a thermogravimetric differential thermal analyzer (STA7200 manufactured by Hitachi High-Tech Science Corporation) when the temperature was raised to 450°C at a rate of 10°C per minute under a nitrogen flow. d50 The weight loss rate is calculated.
[0067] T d50 If the weight loss rate at normal pressure is 1% or less, then the weight loss rate at reduced pressure T d50 It is concluded that the weight loss in the organic semiconductor is due to evaporation, not thermal decomposition. Such an organic semiconductor does not decompose when heated during deposition, i.e., it is a material suitable for deposition. On the other hand, T d50 If the weight loss rate at normal pressure exceeds 1%, d50 The weight loss in the organic semiconductor is considered to be due to thermal decomposition. Since such an organic semiconductor decomposes when heated during deposition, it can be considered to be unsuitable for deposition.
[0068] The organic semiconductor 51a used for the deposition is preferably one having a molecular weight of 300 to 1,000.
[0069] (Fluorine-containing polymer) The fluorine-containing polymer 52a used in the method for producing a porous membrane of this embodiment is a polymer containing fluorine atoms. In the present invention, oligomers are also included in the polymer. That is, the fluorine-containing polymer may be an oligomer.
[0070] The fluorine-containing polymer used in the method for producing a porous membrane of the present embodiment is a fluorine-containing polymer that is soluble in a fluorine-containing solvent. It is advisable to confirm in advance by a preliminary experiment that the fluorine-containing polymer is soluble in a fluorine-containing solvent. The fluorine-containing solvent to be used will be described later.
[0071] The solubility of the fluoropolymer is determined by the following method. 10 g of fluorine-containing polymer is added to 1000 g of fluorine-containing solvent, stirred at 25°C for 24 hours, and then filtered through a polytetrafluoroethylene (PTFE) filter with a nominal mesh size of 1 μm and a diameter of 47 mm. The filtered filter is vacuum-dried at 50°C for 1 hour, and the mass of the dried filter is measured to determine the increase in mass relative to the filter mass before filtration. If the increase in mass is 0.1 g or less, it is considered to have dissolved.
[0072] The fluoropolymer is preferably one that has a sufficient evaporation rate or saturated vapor pressure for deposition at a temperature below the thermal decomposition temperature of the fluoropolymer. The thermal decomposition onset temperature of PTFE, a common fluoropolymer, is about 400°C, and that of Teflon (registered trademark) AF is 350°C.
[0073] The fluoropolymer used in this embodiment is preferably one having a threshold temperature of 340° C. or less as determined under the following conditions. (Measurement Conditions) Fluorine-containing polymer 1×10 -3 When heated at a vacuum of 10 Pa at a rate of 2°C per minute, the evaporation rate is 0.1 g / (m 2 sec) to 0.1g / (m 2 The boundary temperature where the temperature is equal to or higher than the threshold temperature (seconds).
[0074] The saturated vapor pressure at 300° C. of the fluoropolymer used in this embodiment is preferably 0.001 Pa or more, and more preferably 0.002 Pa or more.
[0075] From this viewpoint, the fluorine-containing polymer is preferably a perfluoropolymer which is considered to have small intermolecular interactions, and more preferably a polymer having an aliphatic ring structure in the main chain, which will be described later and is considered to have low crystallinity.
[0076] In this specification, the evaporation rate and saturated vapor pressure (unit: Pa) are values measured by a vacuum differential thermobalance (VAP-9000 manufactured by Advance Riko Co., Ltd.). -3 The temperature was raised at 2°C per minute under a vacuum of 100 Pa, and the evaporation rate at each temperature (unit: g / (m 2 The saturated vapor pressure is calculated using the evaporation rate and molecular weight.
[0077] The weight average molecular weight (hereinafter referred to as "Mw") of the fluorine-containing polymer is preferably from 1,000 to 50,000, more preferably from 1,500 to 40,000, and further preferably from 2,000 to 30,000.
[0078] When the weight average molecular weight is 1000 or more, the Tg of the fluororesin becomes high, and the formed phase-separated structure becomes less likely to collapse.
[0079] On the other hand, when the weight-average molecular weight is 50,000 or less, the vapor deposition source has a saturated vapor pressure that provides a practical layer formation rate (film formation rate), and therefore there is no need to heat the vapor deposition source to a high temperature, specifically, to a temperature above 400°C. If the temperature of the vapor deposition source is too high, the main chain of the fluoropolymer is cleaved during the vapor deposition process, causing the fluoropolymer to have a low molecular weight, resulting in an insufficient strength of the layer formed, and furthermore, defects resulting from the decomposition products are generated, making it difficult to obtain a smooth surface. In addition, it is expected that molecules or ions unintentionally mixed in due to the cleavage of the main chain may affect the conductivity of the film and the luminescence life of the organic EL element. Therefore, when the Mw of the fluoropolymer is in the range of 1,000 to 50,000, the main chain of the fluoropolymer will not be cleaved, and a layer having sufficient strength and a smooth surface can be formed.
[0080] The weight average molecular weight of the fluoropolymer is a value measured using gel permeation chromatography (GPC). First, a PMMA standard sample with a known molecular weight is measured using GPC, and a calibration curve is created from the peak top elution time and molecular weight. Next, the fluoropolymer is measured, and Mw and Mn are obtained from the calibration curve. A mixed solvent of 1,1,1,2,3,4,4,5,5,5-decafluoro-3-methoxy-2-(trifluoromethyl)pentane / hexafluoroisopropyl alcohol (volume ratio 85 / 15) is used as the mobile phase solvent.
[0081] "Polydispersity" refers to the ratio of Mw to the number average molecular weight (hereinafter referred to as "Mn"), i.e., Mw / Mn. From the viewpoint of the stability of the quality of the layer to be formed, the polydispersity (molecular weight distribution) (Mw / Mn) of the fluoropolymer is preferably small, and is preferably 2 or less. The polydispersity of the fluoropolymer is more preferably 1.5 or less, and further preferably 1.2 or less. The theoretical lower limit of the polydispersity is 1. The smaller the polydispersity of the fluoropolymer, the less the fluctuation in deposition conditions becomes, and the more easily a homogeneous phase-separated structure is formed in the film thickness direction.
[0082] Methods for obtaining a fluorine-containing polymer having a small polydispersity include a method of performing controlled polymerization such as living radical polymerization, a molecular weight fractionation purification method using size exclusion chromatography, and a molecular weight fractionation purification method by sublimation purification or supercritical extraction. Of these methods, sublimation purification is preferred in consideration of the stability of the deposition rate when a deposition method is applied to the formation of a layer.
[0083] In this specification, the weight average molecular weight and polydispersity are values measured by gel permeation chromatography (GPC).
[0084] The higher the Tg of the fluoropolymer, the more stable the phase separation structure formed is, and therefore the more preferable. Specifically, the Tg of the fluoropolymer is preferably 30° C. or higher, more preferably 50° C. or higher, and particularly preferably 70° C. or higher. There is no particular upper limit, but the Tg is preferably 350° C., and more preferably 300° C. The higher the Tg of the fluoropolymer, the more easily a stable phase-separated structure is formed.
[0085] When the perfluoropolymer having a fluorine-containing alicyclic structure in the main chain is a perfluoropolymer consisting only of units obtained by cyclic polymerization of perfluoro(3-butenyl vinyl ether), its intrinsic viscosity [η] is preferably 0.01 to 0.14 dl / g, more preferably 0.02 to 0.1 dl / g, and particularly preferably 0.02 to 0.08 dl / g. When [η] is 0.01 dl / g or more, the molecular weight of the fluorine-containing polymer becomes relatively large, and the layer after co-deposition tends to have sufficient heat resistance. On the other hand, when [η] is 0.14 dl / g or less, the molecular weight of the fluorine-containing polymer becomes relatively small, and the saturated vapor pressure that gives a practical film formation speed is obtained.
[0086] In this specification, the intrinsic viscosity [η] (unit: dl / g) is a value measured at a measurement temperature of 30°C using a fluorine-containing solvent, Asahiklin (registered trademark) AC2000 (manufactured by AGC Corporation), as the solvent with an Ubbelohde viscometer (Ubbelohde viscometer, manufactured by Shibata Scientific Co., Ltd.).
[0087] Examples of the fluorine-containing polymer soluble in a fluorine-containing solvent include the following polymers (1) and (2). Polymer (1): A fluorine-containing polymer having no aliphatic ring in the main chain and having a perfluoroalkyl group in the side chain; Polymer (2): A fluorine-containing polymer having an aliphatic ring in the main chain.
[0088] <Polymer (1)> "Having no ring structure in the main chain" means that the carbon atoms constituting the main chain of the fluorine-containing polymer are not carbon atoms constituting a ring skeleton. An example of a polymer that does not have a ring structure in the main chain is a polymer formed by polymerization of a compound having one polymerizable double bond. In this case, the main chain of the polymer is a linear carbon chain formed by the reaction (polymerization) of the polymerizable double bond.
[0089] The perfluoroalkyl group that the polymer (1) has on its side chain is preferably a linear or branched perfluoroalkyl group having 2 to 8 carbon atoms, and particularly preferably a perfluoroalkyl group having 4 to 6 carbon atoms. If the perfluoroalkyl group has 2 or more carbon atoms, it is easily dissolved in a fluorine-containing solvent. If the perfluoroalkyl group has 8 or less carbon atoms, adverse effects are unlikely to occur even if decomposition products are generated.
[0090] Examples of perfluoroalkyl groups include -(CF2)3CF3, -CF2CF(CF3)2, -C(CF3)3, -(CF2)4CF3, -(CF2)2CF(CF3)2, -CF2C(CF3)3, -CF(CF3)CF2CF2CF3, -(CF2)5CF3, -(CF2)3CF(CF3)2, and the like, with -(CF2)3CF3 and -(CF2)5CF3 being particularly preferred.
[0091] An example of the polymer (1) is a polymer having a unit derived from a monomer having one polymerizable double bond and a perfluoroalkyl group at the end (hereinafter also referred to as "monomer (f1)").
[0092] Examples of the monomer (f1) include 2-perfluorohexylethyl acrylate (hereinafter also referred to as "C6FA"), 2-perfluorohexylethyl methacrylate (hereinafter also referred to as "C6FMA"), 2-perfluorobutylethyl acrylate, 3,3,4,4,5,5,6,7,7,7-decafluoro-6-(trifluoromethyl)heptyl acrylate, and 2-perfluorohexylethyl α-chloroacrylate (hereinafter also referred to as "α-ClC6FA").
[0093] The polymer (1) may be a homopolymer of the monomer (f1) or a copolymer of another monomer copolymerizable with the monomer (f1).
[0094] Examples of other monomers copolymerizable with monomer (f1) include (meth)acrylate-based monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, behenyl (meth)acrylate, phenyl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, cyclohexyl (meth)acrylate, and benzyl methacrylate; aromatic hydrocarbon-based vinyl monomers such as styrene and 4-hydroxystyrene; vinyl ether-based monomers such as t-butyl vinyl ether and cyclohexyl vinyl ether; and vinylidene-based monomers such as 1,1-dichloroethylene and 1,1-difluoroethylene. Incidentally, "(meth)acrylate" is a general term for acrylate and methacrylate.
[0095] The polymer (1) may be a synthesized product or a commercially available product.
[0096] <Polymer (2)> The polymer (2) is a fluorine-containing polymer having an aliphatic ring in the main chain. The term "fluoropolymer having an aliphatic ring in the main chain" means that the fluoropolymer has a unit having an aliphatic ring structure, and at least one of the carbon atoms constituting the aliphatic ring is a carbon atom constituting the main chain. The aliphatic ring may be a ring having a heteroatom such as an oxygen atom.
[0097] The "main chain" of a polymer, in the case of a polymer of a monoene having a polymerizable double bond, refers to a chain of carbon atoms derived from the two carbon atoms that constitute the polymerizable double bond. In the case of a cyclopolymerizable diene cyclopolymer, it refers to a chain of carbon atoms derived from four carbon atoms constituting two polymerizable double bonds. Furthermore, in a copolymer of a monoene and a cyclopolymerizable diene, it refers to a chain of carbon atoms derived from the above two carbon atoms of the monoene and the above four carbon atoms of the diene.
[0098] When the monomer of a polymer "having an aliphatic ring in the main chain" is a monoene having an aliphatic ring, one of the monoenes is a monoene having a structure in which one carbon atom constituting the ring skeleton of the aliphatic ring and one carbon atom outside the aliphatic ring are carbon atoms constituting a polymerizable double bond. The main chain of such a monoene polymer contains the two carbon atoms that constituted the polymerizable double bond, and one of the carbon atoms is a carbon atom constituting the ring skeleton of the aliphatic ring. Another type of monoene having an aliphatic ring is a monoene having a structure in which two adjacent carbon atoms constituting the ring skeleton are carbon atoms constituting a polymerizable double bond. The main chain of the polymer of this monoene contains the two carbon atoms that constituted the polymerizable double bond, and these two carbon atoms are carbon atoms constituting the ring skeleton of the aliphatic ring. Furthermore, when the monomer of the polymer "having an aliphatic ring in the main chain" is a diene capable of cyclopolymerization, one carbon atom in each of the four carbon atoms in the two polymerizable double bonds of the diene is bonded to each other to form an aliphatic ring by cyclopolymerization, and the bonds of the other two carbon atoms become two bonds of the resulting unit to form a divalent unit having an aliphatic ring. The main chain of such a diene polymer contains the four carbon atoms that constituted the two polymerizable double bonds in the diene.
[0099] The number of atoms constituting the ring skeleton of the aliphatic ring in the polymer (2) is preferably 4 to 7, and more preferably 5 to 6. That is, the aliphatic ring is preferably a 4- to 7-membered ring, and more preferably a 5- or 6-membered ring. When the aliphatic ring has a heteroatom as an atom constituting the ring, examples of the heteroatom include an oxygen atom and a nitrogen atom, and an oxygen atom is preferred. The number of heteroatoms constituting the ring is preferably 1 to 3, and more preferably 1 or 2.
[0100] The aliphatic ring may or may not have a substituent. The term "optionally having a substituent" means that a substituent may be bonded to an atom constituting the ring skeleton of the aliphatic ring.
[0101] The hydrogen atoms bonded to the carbon atoms constituting the aliphatic ring of the polymer (2) are preferably substituted with fluorine atoms. In addition, when the aliphatic ring has a substituent, and when the substituent has a hydrogen atom bonded to a carbon atom, the hydrogen atom is preferably substituted with a fluorine atom. Examples of the substituent having a fluorine atom include a perfluoroalkyl group, a perfluoroalkoxy group, and =CF2.
[0102] The aliphatic ring in the polymer (2) is preferably a perfluoroaliphatic ring (an aliphatic ring in which all of the hydrogen atoms bonded to carbon atoms, including substituents, are substituted with fluorine atoms).
[0103] Examples of the polymer (2) include the following polymers (21) and (22). Polymer (21): a fluorine-containing polymer having a unit derived from a cyclic fluorine-containing monoene. Polymer (22): A fluorine-containing polymer having units formed by cyclopolymerization of a fluorine-containing diene capable of cyclopolymerization (hereinafter also simply referred to as "fluorine-containing diene").
[0104] Polymer (21): The "fluorine-containing cyclic monoene" refers to a fluorine-containing monomer having one polymerizable double bond between carbon atoms constituting an aliphatic ring, or a fluorine-containing monomer having one polymerizable double bond between a carbon atom constituting an aliphatic ring and a carbon atom outside the aliphatic ring. As the fluorine-containing cyclic monoene, the following compound (1) or compound (2) is preferable.
[0105] [ka] [In the formula, X 1 , X 2 , X 3 , X 4 , Y 1 and Y 2 are each independently a fluorine atom, a perfluoroalkyl group which may contain an ethereal oxygen atom (-O-), or a perfluoroalkoxy group which may contain an ethereal oxygen atom. 3 and X 4 may be bonded to each other to form a ring.
[0106] X 1 , X 2 , X 3 , X 4 , Y 1 and Y 2 The number of carbon atoms of the perfluoroalkyl group in the formula (I) is preferably 1 to 7, and more preferably 1 to 4. The perfluoroalkyl group is preferably linear or branched, and more preferably linear. Specific examples thereof include a trifluoromethyl group, a pentafluoroethyl group, and a heptafluoropropyl group, and more preferably a trifluoromethyl group.
[0107] X 1 , X 2 , X 3 , X 4 , Y 1 and Y 2 The perfluoroalkoxy group in the above formula includes the above perfluoroalkyl group to which an oxygen atom (-O-) is bonded, and a trifluoromethoxy group is particularly preferred.
[0108] In formula (1), X 1 is preferably a fluorine atom. X 2 is preferably a fluorine atom, a trifluoromethyl group, or a perfluoroalkoxy group having 1 to 4 carbon atoms, and particularly preferably a fluorine atom or a trifluoromethoxy group. X 3 and X 4 are each independently preferably a fluorine atom or a perfluoroalkyl group having 1 to 4 carbon atoms, and particularly preferably a fluorine atom or a trifluoromethyl group. X 3 and X 4 may be bonded to each other to form a ring. The number of atoms constituting the ring skeleton of the ring is preferably 4 to 7, and particularly preferably 5 to 6.
[0109] Preferred specific examples of the compound (1) include the compounds (1-1) to (1-5). [ka]
[0110] In formula (2), Y 1 and Y 2 are each independently preferably a fluorine atom, a perfluoroalkyl group having 1 to 4 carbon atoms, or a perfluoroalkoxy group having 1 to 4 carbon atoms, and particularly preferably a fluorine atom or a trifluoromethyl group.
[0111] Preferred specific examples of the compound (2) include the compounds (2-1) and (2-2). [ka]
[0112] The polymer (21) may be a homopolymer of the above-mentioned fluorine-containing cyclic monoene, or a copolymer of the above-mentioned fluorine-containing cyclic monoene and another monomer copolymerizable therewith. However, the proportion of units derived from fluorinated cyclic monoenes to all units in the polymer (21) is preferably at least 20 mol %, more preferably at least 40 mol %, and even more preferably 100 mol %.
[0113] Examples of other monomers copolymerizable with fluorine-containing cyclic monoenes include fluorine-containing dienes, monomers having a reactive functional group in the side chain, tetrafluoroethylene, chlorotrifluoroethylene, perfluoro(methyl vinyl ether), etc. In addition, other monomers copolymerizable with fluorine-containing cyclic monoenes may be the above-mentioned "monomer (f1)" and "other monomers copolymerizable with monomer (f1)."
[0114] Examples of the fluorinated diene include those mentioned in the description of the polymer (22) described below. The polymer obtained by copolymerization of a fluorinated cyclic monoene and a fluorinated diene is referred to as the polymer (21). Examples of the monomer having a reactive functional group in the side chain include a monomer having a polymerizable double bond and a reactive functional group. Examples of the polymerizable double bond include CF2=CF-, CF2=CH-, CH2=CF-, CFH=CF-, CFH=CH-, CF2=C-, and CF=CF-. Examples of the reactive functional group include the same as those described in the description of the polymer (22) below.
[0115] Polymer (22): The "fluorine-containing diene" is a fluorine-containing monomer having two polymerizable double bonds and a fluorine atom, which can undergo cyclic polymerization. As the polymerizable double bond, a vinyl group, an allyl group, an acryloyl group, or a methacryloyl group is preferable. As the fluorine-containing diene, the following compound (3) is preferable. CF2 = CF – Q – CF = CF2 (3).
[0116] In formula (3), Q is a perfluoroalkylene group having 1 to 5 carbon atoms, preferably 1 to 3 carbon atoms, which may contain an ether oxygen atom and may have a branch, in which some of the fluorine atoms may be substituted with halogen atoms other than fluorine atoms. Examples of the halogen atoms other than fluorine atoms include chlorine atoms and bromine atoms.
[0117] Q is preferably a perfluoroalkylene group containing an etheric oxygen atom.In this case, the etheric oxygen atom in the perfluoroalkylene group may be present at one end of the perfluoroalkylene group, may be present at both ends of the perfluoroalkylene group, or may be present between the carbon atoms of the perfluoroalkylene group.From the viewpoint of cyclic polymerization, it is preferable that an etheric oxygen atom is present at one end of the perfluoroalkylene group.
[0118] Specific examples of compound (3) include the following compounds. CF2=CFFOCF2CF=CF2, CF2 = CFOCF(CF3)CF = CF2, CF2=CFFOCF2CF2CF=CF2, CF2 = CFOCF2CF(CF3)CF = CF2, CF2 = CFOCF(CF3)CF2CF = CF2, CF2=CFOCFClCF2CF=CF2, CF2=CFOCCl2CF2CF=CF2, CF2 = CFOCF2OCF = CF2, CF2 = CFOC(CF3)2OCF = CF2, CF2 = CFOCF2CF(OCF3)CF = CF2, CF2=CFCF2CF=CF2, CF2=CFCF2CF2CF=CF2, CF2=CFCF2OCF2CF=CF2.
[0119] Examples of units formed by cyclopolymerization of compound (3) include the following units (3-1) to (3-4). [ka]
[0120] The polymer (22) may be a homopolymer of a fluorinated diene, or a copolymer of a fluorinated diene and another monomer copolymerizable therewith.
[0121] Examples of other monomers copolymerizable with the fluorine-containing diene include monomers having a reactive functional group in the side chain, tetrafluoroethylene, chlorotrifluoroethylene, perfluoro(methyl vinyl ether), and the like.
[0122] A specific example of the polymer (22) is a polymer having p units represented by the following formula (3-1-1), which is obtained by cyclopolymerization of CF2=CFOCF2CF2CF=CF2 (perfluoro(3-butenyl vinyl ether)). In the following, perfluoro(3-butenyl vinyl ether) will be referred to as "BVE."
[0123] [ka]
[0124] In the formula (3-1-1), p is an integer of 5 to 1,000. p is preferably an integer of 10 to 800, and particularly preferably an integer of 10 to 500.
[0125] The functional group at the end of the main chain of the polymer (2) is preferably a functional group having low reactivity, such as an alkoxycarbonyl group or a trifluoromethyl group.
[0126] As the polymer (2), a synthesized product or a commercially available product may be used. Specific examples of the polymer (2) that may be preferred include BVE cyclized polymer (manufactured by AGC: Cytop (registered trademark)), tetrafluoroethylene / perfluoro(4-methoxy-1,3-dioxole) copolymer (manufactured by Solvay: Hyflon (registered trademark) AD), tetrafluoroethylene / perfluoro(2,2-dimethyl-1,3-dioxole) copolymer (manufactured by Dupont: Teflon (registered trademark) AF), and perfluoro(4-methyl-2-methylene-1,3-dioxolane) polymer (MMD polymer).
[0127] In the present invention, the fluorine-containing polymer is preferably the polymer (2), more preferably the polymer (22), and particularly preferably the fluorine-containing polymer represented by the formula (3-1-1) obtained by cyclopolymerization of BVE.
[0128] When the organic semiconductor and the fluorine-containing polymer are co-deposited, a dopant for the organic semiconductor may also be co-deposited.
[0129] As shown in FIG. 5, when an organic semiconductor and a fluorine-containing polymer are co-deposited, it is believed that the organic semiconductor and the fluorine-containing polymer undergo phase separation on the substrate, forming domains 51b of the organic semiconductor and domains 52b of the fluorine-containing polymer.
[0130] The size (diameter) of the domains 52b of the fluorine-containing polymer is considered to fall within a certain numerical range with little variation depending on the relationship between the surface energy of the substrate 50 on which co-deposition is performed and the surface energy of the fluorine-containing polymer. That is, when the fluorine-containing polymer used is easy to spread on the surface of the substrate 50, the domains 52b are considered to be easy to spread widely, and when the fluorine-containing polymer is difficult to spread on the surface of the substrate 50, the diameter of the domains 52b is considered to be easy to become small.
[0131] 6, when the co-evaporation is continued, the organic semiconductor 51a evaporated from the evaporation source 51 is energetically more stable than the domain 52b, and therefore is thought to deposit in the organic semiconductor domain 51b. Similarly, the fluorine-containing polymer 52a evaporated from the evaporation source 52 is energetically more stable than the domain 51b, and therefore is thought to deposit in the fluorine-containing polymer domain 52b.
[0132] As a result, domains 51b of the organic semiconductor that are continuous in the thickness direction of the co-deposited film and domains 52b of the fluorine-containing polymer that are continuous in the thickness direction of the co-deposited film are formed. When the co-deposited film is viewed from the normal direction of the substrate 50, the diameter of the domains 52b does not change significantly in the thickness direction of the co-deposited film and reflects the size of the initial domains 52b formed on the surface of the substrate 50.
[0133] The fact that the co-deposited film 10 is phase-separated into the domains 51b and 52b can be confirmed by the following method. (How to check) The co-deposited film is embedded in epoxy resin and hardened, then cut with an ultramicrotome to prepare ultrathin sections. The ultrathin sections collected on a microgrid are stained with RuO4 and subjected to TEM observation using a transmission electron microscope (HT7700, Hitachi High-Technologies Corporation). The accelerating voltage during observation is 100 kV, and imaging is performed in high-resolution mode.
[0134] 7, the substrate 50 on which the organic semiconductor and the fluorine-containing polymer are co-deposited is immersed in a fluorine-containing solvent 60. In Fig. 7, the substrate 50 is immersed in the fluorine-containing solvent 60 stored in a storage tank 600.
[0135] The fluorine-containing solvent 60 used is one that dissolves the fluorine-containing polymer forming the domains 52b but does not substantially dissolve the organic semiconductor forming the domains 51b. This dissolves and removes the domains 52b, and a porous film 1 formed only of the domains 51b is obtained.
[0136] Here, "substantially" not dissolving means that the solubility of the organic semiconductor in the fluorine-containing solvent 60 used is extremely low compared to the solubility of the fluorine-containing polymer in the fluorine-containing solvent 60, and as a result, the domains 51b are hardly dissolved. By using the fluorine-containing solvent 60 having such properties, it is possible to dissolve the domains 52b without dissolving the domains 51b within a range that does not impair the effects of the invention of the obtained porous film 1. In this sense, the fluorine-containing solvent 60 may dissolve the organic semiconductor constituting the domains 51b within a range that does not impair the effects of the invention.
[0137] Such a fluorine-containing solvent 60 has a fluorine affinity parameter P F It is preferable to use a solvent in which the ratio is equal to or greater than 1. By using such a fluorine-containing solvent 60, it is possible to dissolve the domains 52b of the fluorine-containing polymer without substantially dissolving the domains 51b of the organic semiconductor.
[0138] (Fluorophilic parameter P F ) 30 μL of the fluorine-containing solvent is dropped into a two-phase system of 3 g of toluene and 3 g of perfluoromethylcyclohexane, mixed and allowed to stand overnight, and then the fluorine-containing solvent contained in the toluene and the fluorine-containing solvent contained in the perfluoromethylcyclohexane are measured by gas chromatography. The concentration of the fluorine-containing solvent in the toluene (unit: mL / L) is MP The concentration of the fluorine-containing solvent in the perfluoromethylcyclohexane (unit: mL / L) is M F When the above formula is used, the fluorine-philic parameter P is calculated by the following formula (A). F Let us assume that. P F =M F / M P …(A)
[0139] Examples of the fluorine-containing solvent include the following compounds. 1,1,1,2,2,3,3,4,4,5,5,6,6-Tridecafluorohexane (AC2000, manufactured by AGC Co., Ltd.) (P F =12) 1,1,1,2,2,3,3,4,4,5,5,6,6-Tridecafluorooctane (AC6000, manufactured by AGC Inc.) (P F =5.6) Cytop CT-SOLV100E (AGC Corporation) (P F =8.2) Cytop CT-SOLV180 (AGC Corporation) (P F =∞) HFE7300 (manufactured by 3M) (P F =8.2) 1,1,1,2,2,3,4,5,5,5-Decafluoropentane (Vertre XF, manufactured by Chemours) (P F =3.7) 1H,1H,2H,2H-Perfluorooctanol (P F =1.1) 1,1,2,2-Tetrafluoroethyl-2,2,2-trifluoroethyl ether (AE3000, manufactured by AGC Inc.) (P F =0.6) HCFC-225ca / HCFC-225cb(45 / 55)(P F =0.3) Perfluorobenzene (P F =0.3) Hexafluoro-2-propanol (P F =0.24) 1H,1H,7H-Perfluoroheptanol (P F =0.23) 1H,1H,5H-Perfluoropentanol (P F =0.1)
[0140] By dissolving and removing the fluorine-containing polymer domains 52b, continuous pores 11 extending continuously in the thickness direction of the co-deposited film are formed in the areas where the domains 52b had been formed.
[0141] 7, the substrate 50 on which the organic semiconductor and the fluorine-containing polymer are co-deposited is immersed in the fluorine-containing solvent 60, but the method for dissolving and removing the fluorine-containing polymer is not limited to this. For example, the substrate 50 on which the organic semiconductor and the fluorine-containing polymer are co-deposited may be exposed to the vapor of the fluorine-containing solvent, the fluorine-containing solvent may be sprayed onto the substrate 50 on which the organic semiconductor and the fluorine-containing polymer are co-deposited, or the fluorine-containing solvent may be poured onto the substrate 50 on which the organic semiconductor and the fluorine-containing polymer are co-deposited.
[0142] The formation of the continuous pores 11 in the washed membrane can be confirmed not only by direct observation using an electron microscope photograph, but also indirectly by measuring whether or not any fluorine-containing polymer remains in the membrane.
[0143] That is, the infrared absorption spectrum of the co-deposited film 10 of the organic semiconductor and the fluorine-containing polymer on the substrate 50 is measured by an infrared spectrophotometer (NicoletiS10 manufactured by Thermo Fisher Scientific Co., Ltd.) before and after cleaning with a fluorine-containing solvent. -1 Check the change in absorbance.
[0144] 1200cm -1 When there is no change in the peak intensity, it is judged that the domains 52b of the fluorine-containing polymer remain and therefore the continuous pores 11 are not formed. On the other hand, 1200cm -1When the peak intensity decreases, it is determined that the domains 52b of the fluorine-containing polymer are decreased and continuous pores 11 are formed.
[0145] In addition, the formation of the continuous pores 11 in the co-deposited film can also be confirmed by measuring the refractive index of the film after drying after cleaning. If the continuous pores 11 are formed in the film after cleaning, the refractive index of the film after cleaning will be lower than the refractive index of the organic semiconductor used.
[0146] Next, the fluorine-containing solvent is removed from the washed film. In this step, the fluorine-containing solvent may be removed by heating, reducing pressure, blowing air, or a combination of these. For example, the fluorine-containing solvent can be suitably removed by vacuum drying at a temperature below the glass transition temperature of the organic semiconductor used in the co-deposition. At this time, if the film is heated to a temperature equal to or higher than the glass transition temperature of the organic semiconductor (for example, 100°C or higher), the continuous pores 11 may be crushed.
[0147] In this manner, the porous membrane 1 can be manufactured. According to the porous film 1 having the above-mentioned configuration, it is possible to provide a film using an organic semiconductor as a forming material and having a lower refractive index than the organic semiconductor. Moreover, according to the above-described method for producing the porous film 1, it is possible to easily produce a film using an organic semiconductor as a forming material and having a lower refractive index than the organic semiconductor.
[0148] [Second embodiment] 8 to 10 are explanatory diagrams of a manufacturing method of a porous membrane 2 according to a second embodiment of the present invention. In the following embodiments, components that have already been described are given the same reference numerals, and detailed description thereof will be omitted.
[0149] As shown in Fig. 8, in this embodiment, first, a co-deposited film 10 having an organic semiconductor domain 51b and a fluorine-containing polymer domain 52b is formed on a substrate 50. The organic semiconductor constituting the domain 51b corresponds to the "first organic semiconductor" in the present invention. Also, the co-deposited film 10 corresponds to the "first film" in the present invention.
[0150] Next, co-evaporation is performed using an organic semiconductor 53a different from the first organic semiconductor and a fluorine-containing polymer 54a. The organic semiconductor 53a corresponds to the "second organic semiconductor" in the present invention. The organic semiconductor 53a uses a material that can be co-evaporated like the first organic semiconductor.
[0151] The fluorine-containing polymer 54a used in this case may be the same as or different from the fluorine-containing copolymer constituting the domain 52b. In this embodiment, the fluorine-containing polymer 54a is made of the same material as the fluorine-containing polymer constituting the domain 52b.
[0152] When co-evaporation is further performed using the fluorine-containing polymer 54a and the organic semiconductor 53a after the formation of the co-evaporation film 10, the organic semiconductor 53a is thought to deposit in the domain 51b of the organic semiconductor since it is energetically more stable than the domain 52b. Similarly, the fluorine-containing polymer 54a is thought to deposit in the domain 52b of the fluorine-containing polymer since it is energetically more stable than the domain 51b.
[0153] As a result, a co-deposited film 20 is formed having domains 53b of the organic semiconductor continuous in the thickness direction of the co-deposited film and domains 54b of the fluorine-containing polymer continuous in the thickness direction of the co-deposited film, as shown in Fig. 9. The co-deposited film 20 corresponds to the "second film" in this invention. The domain 53b is continuous with the domain 51b made of the first organic semiconductor in the thickness direction of the co-deposited film, and the domain 54b is continuous with the domain 52b made of the fluorine-containing polymer in the thickness direction of the co-deposited film.
[0154] When forming the co-deposited film 20, the deposition conditions are set so that the ratio of the fluorine-containing polymer to the total of the fluorine-containing polymer and the organic semiconductor in the formed co-deposited film is 20 to 80 volume %. The ratio of the fluorine-containing polymer to the total of the fluorine-containing polymer and the organic semiconductor in the co-deposited films 10 and 20 may be the same or different.
[0155] 10, the substrate 50 on which the co-deposited film 10 and the co-deposited film 20 are formed is immersed in a fluorine-containing solvent 60. As the fluorine-containing solvent 60, the same fluorine-containing solvent as shown in the first embodiment can be used. This makes it possible to dissolve and remove the domains 52b and 54b of the fluorine-containing polymer. By removing the domains 52b and 54b, continuous holes 11 extending continuously in the thickness direction of the co-deposited film are formed in the locations where the domains 52b and 54b had been formed.
[0156] In this manner, the porous membrane 2 can be manufactured. The porous film 2 having the above-mentioned configuration can also provide a film having a lower refractive index than an organic semiconductor, using an organic semiconductor as a forming material. Moreover, by the above-described method for producing the porous film 2, it is also possible to easily produce a film having a lower refractive index than an organic semiconductor by using an organic semiconductor as a forming material.
[0157] Furthermore, in the above-mentioned method for producing the porous film 2, by repeating the co-deposition using an organic semiconductor and a fluorine-containing polymer after the formation of the co-deposition film 20 shown in Fig. 9, it is possible to laminate three or more layers of co-deposition films having organic semiconductor domains and fluorine-containing polymer domains as described above. By removing the fluorine-containing polymer domains from the laminated film thus formed using a fluorine-containing solvent as shown in Fig. 10, it is possible to laminate three or more layers of porous films.
[0158] [Third embodiment] 11 and 12 are explanatory diagrams of a method for producing a porous membrane 3 according to the third embodiment of the present invention.
[0159] 11, after the porous film 1 is formed, a step of depositing an organic semiconductor 55a may be further included. The organic semiconductor 55a is deposited on the porous film 1, and gradually blocks the openings 11a of the continuous pores 11 of the porous film 1. This step corresponds to the "step of blocking the openings" in the present invention. The organic semiconductor 55a may be the same as the organic semiconductor constituting the porous film 1, or may be different.
[0160] As a result, a porous film 3 having a plurality of through holes 13 extending in the film thickness direction is obtained, as shown in Fig. 12. The through holes 13 are closed on the side opposite to the substrate 50.
[0161] In this embodiment, "closing the opening" includes reducing the diameter of the opening 11a as shown by the symbol α in Fig. 11. That is, if the diameter of the opening 11a becomes narrower by carrying out this step than before, the opening is considered to be closed. In this sense, the opening 11a does not have to be completely closed after the step of closing the opening.
[0162] In this manner, the porous membrane 3 can be manufactured. The porous film 3 having the above-mentioned configuration can also provide a film having a lower refractive index than an organic semiconductor, using an organic semiconductor as a forming material. Moreover, by the above-described method for producing the porous film 3, it is also possible to easily produce a film having a lower refractive index than an organic semiconductor by using an organic semiconductor as a forming material.
[0163] [Fourth embodiment] 13 is a cross-sectional schematic diagram showing an organic optoelectronic device (organic EL device) 100 according to a fourth embodiment of the present invention. The organic EL device 100 has a structure in which a substrate 110, an anode 111, a hole injection layer 112, a hole transport layer 113, an emitting layer 114, an electron transport layer 115, an electron injection layer 116, and a cathode 117 are laminated in this order. The organic EL device 100 of this embodiment employs a top emission system in which light L generated in the emitting layer 114 is emitted to the outside via the cathode 117.
[0164] (substrate) The substrate 110 may or may not have optical transparency. The substrate 110 may be made of inorganic materials such as glass, quartz glass, silicon nitride, etc., or organic polymers (resins) such as acrylic resin, polycarbonate resin, etc. Also, as long as the insulating properties of the surface are ensured, a metal material may be used as the substrate 110. The substrate 110 also includes various wirings and driving elements (not shown) that are electrically connected to the organic EL elements.
[0165] (anode) The anode 111 is formed on the substrate 110, and supplies holes to the hole transport layer 113. In addition, the anode 111 has light reflectivity that reflects light emitted from the light emitting layer 114.
[0166] The anode 111 can be made of a conductive metal oxide such as ITO (Indium Tin Oxide) or IZO (Indium Zinc Oxide). In order to impart light reflectivity to the anode 111, a reflective film made of a metal material is provided on the substrate 110 side of the anode 111. In other words, the anode 111 has a laminated structure of a layer made of a conductive metal oxide and the reflective film. The anode 111 may be made of silver.
[0167] The thickness of the anode 111 is not particularly limited, but is preferably 30 to 300 nm, and is, for example, 100 nm.
[0168] (Hole injection layer) The hole injection layer 112 is formed between the anode 111 and the hole transport layer 113. The hole injection layer 112 has a function of facilitating the injection of holes from the anode 111 to the hole transport layer 113. Note that the hole injection layer 112 does not necessarily have to be formed. The hole injection layer 112 can be formed using the hole injection materials described above.
[0169] The thickness of the hole injection layer 112 is not particularly limited, but is preferably 1 to 100 nm, and is, for example, 5 nm.
[0170] (Hole transport layer) The hole transport layer 113 is formed on the hole injection layer 112. The hole transport layer 113 has a function of efficiently transporting holes injected from the anode 111 toward the light emitting layer 114. The hole transport layer 113 can be formed using the hole transport material described above.
[0171] The hole transport layer 113 has an absorption coefficient of 5000 cm in the wavelength range of 450 nm to 800 nm. -1 Preferably, it is less than 1000 cm -1 It is more preferable that the absorption band is equal to or less than 100 nm, and it is particularly preferable that the absorption band is not present in the above wavelength range. The absorption coefficient of each layer constituting the hole transport layer 113 is 5000 cm -1 When the light passes through a hole transport layer having a thickness of 100 nm once, 5% of the light is absorbed, assuming that the total amount of light before passing through is 100%. Inside the organic EL element, multiple interference of light causes accumulation of loss due to absorption of light when passing through the hole transport layer 113. Therefore, light absorption when passing through the hole transport layer is a factor that greatly reduces the light extraction efficiency. It is extremely important to use a hole transport layer with sufficiently low light absorption so as not to impair the luminous efficiency of the organic EL element. By not impairing the luminous efficiency of the organic EL element, the energy utilization efficiency is increased, and heat generation due to light absorption is suppressed, resulting in a longer element life.
[0172] The thickness of the hole transport layer 113 is not particularly limited, but is preferably 10 nm to 250 nm, and more preferably 20 nm to 150 nm.
[0173] (Light Emitting Layer) The light-emitting layer 114 is formed in contact with the hole transport layer 113. In the light-emitting layer 114, holes injected from the anode 111 and electrons injected from the cathode 117 recombine to emit photons and emit light. The emission wavelength at that time is determined by the material from which the light-emitting layer 114 is formed. The light-emitting layer 114 corresponds to the "active layer" in the present invention.
[0174] The light-emitting layer 114 may be made of any of known materials, such as a fluorescent material, a thermally activated delayed fluorescence (TADF) material, or a phosphorescent material. The materials for forming the light-emitting layer may be used in combination of two or more kinds, and are appropriately selected according to the desired emission wavelength.
[0175] Examples of materials for forming the light-emitting layer 114 include, but are not limited to, the following materials. Luminescent guest materials such as (E)-2-(2-(4-(dimethylamino)styryl)-6-methyl-4H-pyran-4-ylidene)malononitrile (DCM), 4-(dicyanomethylene)-2-methyl-6-julolidyl-9-enyl-4H-pyran (DCM2), Rubrene, Coumarin6, Ir(ppy)3, (ppy)2Ir(acac) Phosphorescent host materials such as 4-4'-bis(9H-carbazol-9-yl)biphenyl (CBP) and 3,3'-di(9H-carbazol-9-yl)-1,1'-biphenyl (mCPB) Fluorescent host materials such as ADN and Alq3 Polymer materials such as polyphenylene vinylene (PPV) and MEH-PPV
[0176] The thickness of the light-emitting layer 114 is not particularly limited, but is preferably 10 to 30 nm. The thickness of the light-emitting layer 114 is, for example, 15 nm.
[0177] (electron transport layer) The electron transport layer 115 is formed in contact with the light emitting layer 114. The electron transport layer 115 has a function of efficiently transporting electrons injected from the cathode 117 toward the light emitting layer 114. The electron transport layer 115 can be formed using the electron transport materials described above. The thickness of the electron transport layer 115 is not particularly limited, but is preferably 30 to 80 nm, and is, for example, 60 nm.
[0178] (electron injection layer) The electron injection layer 116 is provided between the cathode 117 and the electron transport layer 115. The electron injection layer 116 has a function of facilitating the injection of electrons from the cathode 117 to the electron transport layer 115. The electron injection layer 116 can be formed from the above-mentioned electron injection materials. The electron injection layer 116 does not necessarily have to be formed.
[0179] The thickness of the electron injection layer 116 is not particularly limited, but is preferably 0.5 to 2 nm, and is, for example, 1 nm.
[0180] (cathode) The cathode 117 is formed in contact with the electron injection layer 116. The cathode 117 has a function of injecting electrons into the electron injection layer 116. A known material can be used to form the cathode 117. For example, a MgAg electrode or an Al electrode can be used as the material to form the cathode 117. A buffer layer such as LiF may be formed on the surface of the Al electrode. The cathode 117 is a semi-transparent film formed thin enough as a whole to reflect a part of the light emitted from the light-emitting layer 114 and transmit the rest.
[0181] The thickness of the cathode 117 is not particularly limited, but is preferably 5 to 30 nm, for example.
[0182] (Microcavity structure) In the organic EL element 100 of this embodiment, the anode 111 and the cathode 117 form an optical resonance structure (microcavity) that resonates light between the anode 111 and the cathode 117. Between the anode 111 and the cathode 117, light generated in the light-emitting layer 114 is repeatedly reflected, and light with a wavelength that matches the optical path length between the anode 111 and the cathode 117 resonates and is amplified. On the other hand, light with a wavelength that does not match the optical path length between the anode 111 and the cathode 117 is attenuated. The "optical path length" here is calculated using the wavelength of the desired light emitted outside the element and the refractive index of each layer at the wavelength of the desired light.
[0183] The optical path length between the anode 111 and the cathode 117 is set to, for example, an integer multiple of the central wavelength of the light L generated in the light-emitting layer 114. In this case, the light L emitted from the light-emitting layer 114 is amplified as it approaches the central wavelength and is attenuated as it deviates from the central wavelength, before being emitted to the outside of the organic EL element 100. In this way, the light L emitted from the organic EL element 100 has a narrow half-width of the emission spectrum and improved color purity.
[0184] The microcavity structure utilizes the resonance caused by the fixed-end reflection between the cathode and anode at both ends. Therefore, the desired microcavity structure can be formed when the optical path length from the light-emitting position to the anode is an integral multiple of 1 / 4 of the wavelength λ of the desired light to be emitted outside the element, and the optical path length from the light-emitting position to the cathode is an integral multiple of 1 / 4 of the wavelength λ of the desired light to be emitted outside the element.
[0185] The organic EL element 100 of this embodiment employs the above-mentioned porous film in at least one of the hole injection layer 112, the hole transport layer 113, the light-emitting layer 114, the electron transport layer 115, and the electron injection layer 116. The hole injection layer 112, the hole transport layer 113, the light-emitting layer 114, the electron transport layer 115, and the electron injection layer 116 may hereinafter be collectively referred to as "organic semiconductor layers." Therefore, the hole injection layer 112, the hole transport layer 113, the light emitting layer 114, the electron transport layer 115, and the electron injection layer 116 can have a low refractive index, and the light extraction efficiency and external quantum efficiency can be improved compared to when these layers are not porous films. As a result, compared to conventional organic EL elements in which the organic semiconductor layer is not a porous film, the same amount of light emission as conventional organic EL elements can be obtained with less input power.
[0186] Furthermore, when adjacent organic semiconductor layers are both porous films, it is preferable to use a manufacturing method in which co-deposited films corresponding to the respective organic semiconductor layers are laminated and the fluorine-containing polymer is removed all at once, as shown in the above-mentioned second embodiment. Specifically, for example, when the hole injection layer 112 and the hole transport layer 113 are both porous films, it is preferable to co-deposit a hole injection material and a fluorine-containing polymer to form a co-deposited film (first film), then co-deposit a hole transport material and a fluorine-containing polymer to form a co-deposited film (second film), and then remove the fluorine-containing polymer contained in the first film and the second film all at once.
[0187] Furthermore, when the hole transport layer 113 is a porous film, a step of blocking the openings of the continuous holes in the hole transport layer 113 may be performed as described in the third embodiment after the formation of the hole transport layer 113 and before the formation of the light emitting layer 114. This prevents a part of the light emitting layer 114 from entering the continuous holes in the hole transport layer 113 when the light emitting layer 114 is formed, and it is possible to eliminate locations in the light emitting layer 114 where charge transfer is likely to concentrate.
[0188] In addition, when the electron transport layer 115 is a porous film, it is preferable to form the electron transport layer 115 after forming the light emitting layer 114 by depositing only the electron transport material on the light emitting layer 114 to form a layer of the electron transport material, and then co-deposit the electron transport material and the fluorine-containing polymer. This makes it possible to eliminate locations in the light emitting layer 114 where charge transfer is likely to concentrate.
[0189] According to the organic EL element 100 having the above-mentioned configuration, since the organic semiconductor layer is a porous film, the external quantum efficiency is improved, and the organic EL element has low power consumption.
[0190] [Fifth embodiment] FIG. 14 is an explanatory diagram of an organic EL element 200 according to a fifth embodiment of the present invention, and corresponds to FIG.
[0191] The organic EL element 200 has a structure in which a substrate 210, an anode 211, a hole injection layer 112, a hole transport layer 113, an emitting layer 114, an electron transport layer 115, an electron injection layer 116, and a cathode 217 are laminated in this order. The organic EL element 200 of this embodiment employs a bottom emission system in which light L generated in the emitting layer 114 is emitted to the outside through the anode 211 and the substrate 210.
[0192] The substrate 210 is optically transparent. The substrate 210 can be made of inorganic materials such as glass, quartz glass, and silicon nitride, or organic polymers (resins) such as acrylic resin and polycarbonate resin. Also, a composite material formed by laminating or mixing the above materials can be used as long as it is optically transparent.
[0193] The anode 211 is formed on the substrate 210, and supplies holes to the hole transport layer 113. The anode 211 can be formed from a light-transmitting conductive metal oxide such as ITO or IZO.
[0194] The cathode 217 is formed in contact with the electron injection layer 116. The cathode 217 has a function of reflecting light L isotropically emitted from the light emitting layer 114 and directing the light L toward the anode 211. The thickness of the cathode 217 is not particularly limited, but is preferably 30 to 300 nm, and is, for example, 100 nm.
[0195] In the organic EL element 200 having such a configuration, similarly to the organic EL element 100 shown in the fourth embodiment, the above-mentioned porous film is used in at least one of the hole injection layer 112, the hole transport layer 113, the light emitting layer 114, the electron transport layer 115, and the electron injection layer 116. This can improve the light extraction efficiency.
[0196] The organic EL element 200 having the above-mentioned configuration also has an organic semiconductor layer that is a porous film, and therefore has improved external quantum efficiency and consumes less power.
[0197] A wavelength conversion layer including quantum dots may be disposed in the light emission direction in the organic EL element 100 or the organic EL element 200. By including such a wavelength conversion layer, the organic EL element has improved color purity of emitted light.
[0198] In the organic EL element 100 or the organic EL element 200, quantum dots may be used as a material for forming the light-emitting layer 114. Quantum dots refer to nanoscale semiconductor crystals that have unique optical properties according to quantum mechanics. Quantum dots are usually single crystal particles with a diameter of 2 to 10 nm. Since the band gap of quantum dots changes depending on the crystal size (=particle size), the band gap can be adjusted by adjusting the particle size, and a desired emission wavelength can be obtained.
[0199] As the quantum dots, colloidal quantum dots that can be dispersed in a solution can be used, and such colloidal quantum dots can be formed into a film by using a general wet coating technique. The type of quantum dots is not particularly limited, and perovskite quantum dots, carbon-based quantum dots, alloy-type quantum dots, core-shell type quantum dots, and core-type quantum dots can be used.
[0200] In addition, in the above-mentioned embodiment, an organic EL element has been described as an example of an organic optoelectronic element, but the organic optoelectronic element to which the porous film of the present invention is applied is not limited to an organic EL element.
[0201] The organic optoelectronic device of the present invention may be, for example, an organic semiconductor laser. A known configuration can be adopted for the organic semiconductor laser. By adopting the above-mentioned porous film in the organic semiconductor layer (at least one layer among the hole injection layer, the hole transport layer, the electron injection layer, and the electron transport layer) of the organic semiconductor laser, the organic semiconductor laser has an improved external quantum efficiency.
[0202] The organic optoelectronic device of the present invention may be, for example, a light-receiving element such as a photosensor or a solar cell. As the photosensor and the solar cell, a known configuration can be adopted in which holes and electrons generated in the active layer (light-receiving layer) according to the intensity of light received by the active layer are transferred to the cathode and the anode via the organic semiconductor layer.
[0203] By adopting the above-mentioned porous film in the active layer of the photosensor and solar cell, it is possible to suppress the internal reflection of the light taken in, and to increase the amount of light reaching the active layer. Furthermore, at least one layer among the hole injection layer, hole transport layer, electron injection layer, active layer, and electron transport layer may be the above-mentioned porous film.
[0204] These will result in photosensors with improved detection performance and solar cells with improved power generation efficiency.
[0205] Although the preferred embodiment of the present invention has been described above with reference to the attached drawings, it goes without saying that the present invention is not limited to the above embodiment. The shapes and combinations of the components shown in the above embodiment are merely examples, and various modifications can be made based on design requirements, etc., without departing from the spirit of the present invention. EXAMPLES
[0206] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.
[0207] In this embodiment, evaluation was performed by the following methods.
[0208] "Method for measuring refractive index of fluorine-containing polymer" The refractive index of the fluorine-containing polymer is a value measured in accordance with JIS K 7142.
[0209] "Methods for measuring weight-average molecular weight (Mw), number-average molecular weight (Mn) and polydispersity (Mw / Mn) of fluoropolymers" The weight average molecular weight of the fluoropolymer was measured using gel permeation chromatography (GPC). First, a PMMA standard sample with a known molecular weight was measured using GPC, and a calibration curve was created from the peak top elution time and molecular weight. Next, the fluoropolymer was measured, and the weight average molecular weight (Mw) and number average molecular weight (Mn) were obtained from the calibration curve. The polydispersity (Mw / Mn) was calculated from Mw and Mn. A mixed solvent of 1,1,1,2,3,4,4,5,5,5-decafluoro-3-methoxy-2-(trifluoromethyl)pentane / hexafluoroisopropyl alcohol (volume ratio 85 / 15) was used as the mobile phase solvent.
[0210] "Method for measuring intrinsic viscosity [η] of fluoropolymers" The intrinsic viscosity [η] of the fluoropolymer was measured at a measurement temperature of 30° C. using Asahiklin (registered trademark) AC2000 (manufactured by AGC) as a solvent with an Ubbelohde viscometer (Ubbelohde viscometer manufactured by Shibata Scientific Co., Ltd.).
[0211] "Method of measuring vapor pressure and evaporation rate of fluoropolymers" The evaporation rate and saturated vapor pressure were measured at 340°C or less using a vacuum differential thermobalance (Advance Riko Co., Ltd.: VPE-9000). 50 mg of fluoropolymer was placed in a cell with an inner diameter of 7 mm, and 1 × 10 -3 At a vacuum of 100 Pa, the temperature is increased at 2°C per minute, and the evaporation rate at each temperature below 340°C is g / m 2 ·sec were measured. The evaporation rate and molecular weight were used to calculate the saturated vapor pressure.
[0212] "Method for measuring threshold temperature of fluoropolymer" The evaporation rate measured by the above method is 0.1 g / (m 2 sec) to 0.1g / (m2 The boundary temperature where the temperature was equal to or higher than 1.0 s was set as the threshold temperature.
[0213] "Method for determining whether or not organic semiconductor deposition is possible" The measurements were performed using a vacuum differential thermobalance (Advance Riko Co., Ltd.: VPE-9000). 50 mg of the organic semiconductor was placed in a cell with an inner diameter of 7 mm, and the temperature was measured at 1 × 10 -3 ~1×10 -4 The weight loss rate (%) of the organic semiconductor was measured when the temperature was increased to 500°C at a rate of 2°C per minute under a vacuum of 100 Pa. The temperature at which the weight loss rate reached 50% (T d50 ) was sought.
[0214] Next, the weight loss rate of the organic semiconductor was measured using a thermogravimetric differential thermal analyzer (STA7200 manufactured by Hitachi High-Tech Science Corporation) when the temperature was raised to 450°C at a rate of 10°C per minute under a nitrogen flow. d50 The weight loss rate was calculated.
[0215] T d50 If the weight loss rate at normal pressure is 1% or less, then the weight loss rate at reduced pressure T d50 It is concluded that the weight loss in the organic semiconductor is due to evaporation, not thermal decomposition. Such an organic semiconductor does not decompose when heated during deposition, i.e., it is a material suitable for deposition.
[0216] On the other hand, T d50 If the weight loss rate at normal pressure exceeds 1%, d50 The weight loss in the organic semiconductor is considered to be due to thermal decomposition. Since such an organic semiconductor decomposes when heated during deposition, it can be considered to be unsuitable for deposition.
[0217] "Method of determining porosity" The infrared absorption spectrum of the co-deposited film of the organic semiconductor and the fluorine-containing polymer formed on the silicon substrate before and after washing with a fluorine-containing solvent was measured using an infrared spectrophotometer (NicoletiS10 manufactured by Thermo Fisher Scientific Co., Ltd.). The peak at wavenumber 1200 cm, which is derived from CF specific to the fluorine-containing polymer, was observed. -1The change in absorbance at 1200cm was evaluated. -1 If there was no change in the peak intensity, it was judged as impossible to make porous (×), and if the peak intensity decreased and could not be confirmed, it was judged as possible to make porous (◯).
[0218] "Method for confirming the phase separation structure of co-deposited films" The organic semiconductor and fluoropolymer co-deposited film sample formed on the COP film was embedded in epoxy resin, hardened, and then cut with an ultramicrotome to prepare ultrathin sections. The ultrathin sections collected on a microgrid were stained with RuO4 and subjected to TEM observation. A Hitachi High-Technologies Corporation HT7700 was used for TEM observation, with an accelerating voltage of 100kV and high-resolution mode for imaging.
[0219] "Method for confirming the vertical alignment of porous films" A porous film sample formed on a silicon substrate was evaluated by GI-SAXS measurement. The measurement was performed at BL-6A of the High Energy Accelerator Research Organization. The wavelength of the incident X-ray was 1.5 Å, the incident angle was 0.16°, the detector was PILATUS3 1M, and the camera length was 2.5 m.
[0220] "Method for measuring the d value (interplanar spacing) of porous membranes" The cluster structure of the porous film sample formed on the COP film was evaluated by small angle X-ray scattering (SAXS). The Aichi Synchrotron BL8S3 was used for the incident X-rays, with a wavelength of 1.5 Å (8.2 keV), a beam size of approximately 850 μm × 280 μm, a camera length of 1121.52 mm, and an R-AXISIV (imaging plate) detector, and the exposure time was 60 seconds. The data was processed using Fit 2D software, which circularly averaged the two-dimensional data to convert it to one dimension, and then performed background correction, transmittance correction, and air scattering correction when reading the IP. Sample thickness correction was omitted due to low accuracy and location unevenness.
[0221] "Method for measuring thickness and refractive index of porous films and organic semiconductor films" Using a multi-angle spectroscopic ellipsometry (M-2000U manufactured by J.A. Woollam Co.), measurements were performed on a film on a silicon substrate, changing the angle of incidence of light in 5 degree increments in the range of 45 to 75 degrees. At each angle, the ellipsometry parameters Ψ and Δ were measured at approximately 1.6 nm intervals in the wavelength range of 450 to 800 nm. Using the above measurement data, a fitting analysis was performed on the dielectric function of the organic semiconductor using the Cauchy model, and the refractive index and film thickness of the porous film and organic semiconductor film for light with a wavelength of 600 nm were obtained.
[0222] "Method for calculating the porosity of a porous film" The porosity of the porous film was calculated from the following formula assuming that the film is made of an organic semiconductor and air. The refractive index of air (n a ) was 1, and the refractive indexes of the organic semiconductor and the porous film were determined by the above-mentioned method. Porosity (%)=(n p -n o ) / (n a -n o ) x 100 n p : Refractive index of porous film n o : Refractive index of organic semiconductors n a : Refractive index of air
[0223] "Method for evaluating JV characteristics of conductive evaluation element" A voltage was applied using a source meter (Keithley: Keithley (registered trademark) 2401) with the ITO (indium tin oxide) side as the anode and the aluminum side as the cathode, and the current flowing through the conductivity evaluation element for each voltage was measured.
[0224] "Method for verifying the light extraction efficiency of organic EL elements" <Verification of the effect through optical calculations> In order to verify the effect of improving the light extraction efficiency by making the organic semiconductor layer that constitutes the organic EL element nanoporous and thereby reducing the refractive index, a simulation was performed using Setfos4.6 (manufactured by Cybernet Inc.).
[0225] [Synthesis Example 1] 30 g of perfluoro(3-butenyl vinyl ether) (BVE), 30 g of 1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluorohexane (1H-PFH), 0.5 g of methanol, and 0.44 g of diisopropyl peroxydicarbonate (IPP) were weighed and placed in a glass reactor with an internal volume of 50 ml. After the inside of the vessel was replaced with high-purity nitrogen gas, polymerization was carried out at 40°C for 24 hours. The obtained solution was subjected to desolvation under conditions of 666 Pa (absolute pressure) and 50°C, and 28 g of a fluorine-containing polymer was obtained. The intrinsic viscosity [η] of the obtained fluorine-containing polymer was 0.04 dl / g.
[0226] Next, the obtained fluoropolymer was heated in an oven at 300° C., and then treated by the method described in paragraph
[0040] of JP-A-11-152310 to replace the unstable terminal groups with —CF3 groups using fluorine gas, thereby obtaining a fluoropolymer A.
[0227] The resulting fluoropolymer A had a refractive index of 1.34 for light with a wavelength of 600 nm, and an intrinsic viscosity [η] of 0.04 dl / g. The fluoropolymer A had Mw of 9000, Mn of 6000, Mw / Mn of 1.5, and a saturated vapor pressure at 300° C. of 1×10 -3 Under a reduced pressure of 0.002 Pa and 300°C, the evaporation rate is 1×10 -3 0.08g / (m2) under reduced pressure 2 · seconds), 1×10 -3 The evaporation rate is 0.1 g / (m) under reduced pressure of 10 Pa. 2 The threshold temperature for exceeding the threshold temperature (Ts) was 320°C.
[0228] [Synthesis Example 2] 2 g of perfluoro(4-methyl-2-methylene-1,3-dioxolane) (MMD), 6 g of 1H-PFH, 0.4 g of methanol, and 0.2 g of IPP were weighed and placed in a glass reactor with an internal volume of 50 ml. After the inside of the vessel was replaced with high-purity nitrogen gas, polymerization was carried out at 40°C for 24 hours. The solvent was removed from the obtained solution at 666 Pa (absolute pressure) and 50°C to obtain 1 g of polymer.
[0229] The obtained polymer was then heated in an oven at 300° C., immersed in methanol, and heated in an oven at 75° C. for 20 hours to replace the unstable terminal groups with methyl ester groups, thereby obtaining a fluorine-containing polymer B.
[0230] The resulting fluoropolymer B had a refractive index of 1.33 for light with a wavelength of 600 nm, Mw of 11,300, Mn of 9,300, Mw / Mn of 1.2, and a saturated vapor pressure at 300°C of 1×10 -3 Under a reduced pressure of 0.007 Pa and 300°C, the evaporation rate is 1×10 -3 0.10g / (m2) at reduced pressure 2 · seconds), 1×10 -3 The evaporation rate is 0.1 g / (m) under reduced pressure of 10 Pa. 2 The threshold temperature for exceeding the threshold temperature (°C) was 290°C.
[0231] [Synthesis Example 3] A jacketed polymerization tank (made of stainless steel) with an internal volume of 1.351 L was degassed, and 617 g of AE-3000 (manufactured by Asahi Glass Co., Ltd.), 145 g of perfluoropropoxyethylene (PPVE), 106 g of tetrafluoroethylene (TFE), and 35.9 g of methanol were weighed and charged into the polymerization tank. The temperature was kept at 60°C, and 18.9 mL of a 7.77 mass% solution of t-butyl peroxypivalate (PBPV) (solvent: AE-3000) was charged to initiate polymerization. During polymerization, TFE was introduced into the polymerization tank, and the polymerization pressure was kept at 1.04 MPa in gauge pressure. The atmospheric pressure was 133.322 Pa.
[0232] Since the polymerization pressure decreased with the progress of the polymerization, TFE was continuously charged so that the polymerization pressure was kept almost constant. The polymerization was terminated when the amount of TFE introduced reached 121 g, to obtain a fluorine-containing copolymer X. The composition of the obtained polymer was PPVE unit:TFE unit=4:96 (mol%).
[0233] The obtained polymer was then heated in an oven at 330°C, immersed in methanol, and heated in an oven at 75°C for 40 hours to replace the unstable terminal groups with methyl ester groups, thereby obtaining a fluorine-containing polymer C.
[0234] The refractive index of the obtained fluoropolymer C to light with a wavelength of 600 nm was 1.34, and the evaporation rate at 300°C was 1×10 -3 0.10g / (m2) at reduced pressure 2 · seconds), 1×10 -3 The evaporation rate is 0.1 g / (m) under reduced pressure of 10 Pa. 2 The threshold temperature above which the thermal shock occurred (>100 s) was 300 °C.
[0235] [Determination of whether or not organic semiconductors can be vapor-deposited] The organic semiconductors shown in Table 1 below were evaluated for suitability for deposition using the above-mentioned method. The evaluation results are shown in Table 1. In the judgment column, d50 If the weight loss rate at normal pressure is 1% or less and deposition is possible, the result is marked as "○"; d50 When the weight loss rate at normal pressure exceeds 1% and deposition is not possible, the mark "X" is entered.
[0236] [Table 1]
[0237] As shown in Table 1, each organic semiconductor with a molecular weight of 300 to 1000 has a T d50 The weight loss rate at normal pressure was small, and it was determined that the material would not decompose under the deposition conditions, and deposition was therefore possible. On the other hand, P3HT with a molecular weight of 54,000 is T d50 The weight loss rate at normal pressure exceeded 1%, which indicated that decomposition occurred under the deposition conditions, and it was found that deposition was not possible.
[0238] <Evaluation 1: Evaluation of porous membrane> [Example 1-1] A silicon substrate cut into a size of about 2.5 cm square and a COP film (ZF16, 100 μm thick, manufactured by Zeon Corporation) were placed in a vacuum deposition machine and heated at a pressure of 10 -4 2TNATA and the fluorine-containing polymer A were co-deposited under a reduced pressure of 0.1 Pa or less to obtain a co-deposited film having a thickness of about 100 nm. The deposition was adjusted so that the volume ratio of 2TNATA to the fluorine-containing polymer in the co-deposited film was 80: 20. The total deposition rate of the two materials was 0.2 nm / sec. The obtained co-deposition film was then transferred to the silicon substrate or COP film using AC2000 (AGC Corporation, P F =12) for 5 minutes, and then vacuum dried at room temperature for 5 minutes to obtain the porous membrane of Example 1-1.
[0239] [Example 1-2] A porous film of Example 1-2 was obtained in the same manner as in Example 1-1, except that the volume ratio of 2TNATA to the fluorine-containing polymer in the co-deposited film was adjusted to 50:50. For the co-deposited film prepared in Example 1-2, it was confirmed by the above-mentioned method that 2TNATA and the fluoropolymer A were phase-separated. Fig. 15 is a cross-sectional TEM photograph of the co-deposited film prepared in Example 1-2. The symbol A in Fig. 15 is the co-deposited film. As shown in the figure, it was confirmed that a phase-separated structure oriented in the film thickness direction was formed in the co-deposited film.
[0240] [Example 1-3] A porous film of Example 1-3 was obtained in the same manner as in Example 1-1, except that the volume ratio of 2TNATA to the fluorine-containing polymer in the co-deposited film was adjusted to 20:80.
[0241] [Example 1-4] A co-deposition film was obtained in the same manner as in Example 1-1, except that the volume ratio of 2TNATA to the fluorine-containing polymer was adjusted to 60:40. The obtained co-deposited film was exposed to refluxing vapor of AC2000 to remove the fluoropolymer, thereby obtaining the porous film of Example 1-4.
[0242] [Example 1-5] A co-deposition film was obtained in the same manner as in Example 1-1, except that the volume ratio of 2TNATA to the fluorine-containing polymer was adjusted to 40:60. The resulting co-deposited film was spin-cleaned using AC2000 at 200 rpm for 60 seconds, and then spin-dried at 2000 rpm for 30 seconds to obtain the porous film of Example 1-5.
[0243] [Example 1-6] The fluorine-containing solvent in which the co-deposition film is immersed is HFE7300 (manufactured by 3M, P F = 8.2), the porous membrane of Example 1-6 was obtained in the same manner as in Example 1-2.
[0244] [Example 1-7] A porous membrane of Example 1-7 was obtained in the same manner as in Example 1-2 except that α-NPD was used instead of 2TNATA and that fluoropolymer B was used instead of fluoropolymer A.
[0245] [Example 1-8] A porous membrane of Example 1-8 was obtained in the same manner as in Example 1-2, except that HT211 was used instead of 2TNATA.
[0246] [Example 1-9] A porous membrane of Example 1-9 was obtained in the same manner as in Example 1-2, except that Tris-PCz was used instead of 2TNATA.
[0247] [Example 1-10] A porous membrane of Example 1-10 was obtained in the same manner as in Example 1-2, except that TPBi was used instead of 2TNATA.
[0248] [Example 1-11] A porous membrane of Example 1-11 was obtained in the same manner as in Example 1-2, except that mCBP was used instead of 2TNATA.
[0249] [Example 1-12] A silicon substrate cut into a size of about 2.5 cm square was placed in the vacuum deposition machine and heated to a pressure of 10 -42TNATA was evaporated under reduced pressure of 0.1 Pa or less (volume ratio of 2TNATA to fluorine-containing polymer was 100:0) to obtain a film of Example 1-12 having a thickness of about 100 nm. The deposition rate was 0.1 nm / sec.
[0250] [Example 1-13] A membrane of Example 1-13 was obtained in the same manner as in Example 1-2 except that fluoropolymer C was used instead of fluoropolymer A.
[0251] [Example 1-14] An attempt was made to prepare a porous film in the same manner as in Example 1-2, except that P3HT was used instead of 2TNATA. However, P3HT did not reach the desired deposition rate and was thermally decomposed on the deposition boat, so a co-deposition film was not obtained.
[0252] Among the above-mentioned Examples 1-1 to 1-14, Examples 1-1 to 1-11 correspond to Examples, and Examples 1-12 to 1-14 correspond to Comparative Examples.
[0253] The results of evaluation of Examples 1-1 to 1-14 by the above-mentioned methods are shown in Tables 2 and 3. In addition, Table 4 shows the refractive indexes of the organic semiconductors used in Examples 1-1 to 1-14. In the column for porosity in Table 3, the results are shown for the 1200 cm -1 Check the change in absorbance at 1200cm -1 If there was no change in the peak intensity, it was marked "X" indicating that porosity could not be achieved, and if the peak intensity decreased and could not be confirmed, it was marked "O" indicating that porosity could be achieved.
[0254] [Table 2]
[0255] [Table 3]
[0256] [Table 4]
[0257] As a result of the evaluation, in Example 1-13, 1200 cm -1 No change was observed in the peak intensity, confirming that the porous structure could not be formed. On the other hand, in Examples 1-1 to 1-11, -1 It was confirmed that the peak intensity of the organic semiconductor film in Examples 1-1 to 1-11 was decreased and the peak could not be confirmed, and thus it was confirmed that the porous films in Examples 1-1 to 1-11 could be made to have a refractive index lower than that of the organic semiconductor used. In addition, the porous films of Examples 1-4 to 1-9 and 1-11 were produced by the same production method as Examples 1-1 to 1-3 and 1-10, and it is believed that the through holes are formed in a direction perpendicular to the substrate.
[0258] <Evaluation 2: Conductivity evaluation of porous film> [Example 2-1] A glass substrate on which a 2 mm-wide strip of ITO (indium tin oxide) was formed was ultrasonically cleaned using a neutral detergent, acetone, and isopropyl alcohol, in that order, and then boiled and cleaned in isopropyl alcohol. After that, any deposits on the surface of the ITO film were removed using ozone treatment. After cleaning, the substrate was placed in a vacuum deposition machine and subjected to a pressure of 10 -4 2TNATA and the fluorine-containing polymer A were co-deposited under a reduced pressure of 0.1 Pa or less to obtain a co-deposited film having a thickness of about 100 nm. The deposition was adjusted so that the volume ratio of 2TNATA to the fluorine-containing polymer in the co-deposited film was 50:50. The total deposition rate of the two materials was 0.2 nm / sec.
[0259] The obtained co-deposited film was immersed together with the glass substrate in AC2000 for 5 minutes in a glove box, and then vacuum dried at room temperature for 5 minutes to obtain a porous film. Then, a pressure of 10 -4 A 20 nm layer of 2TNATA was deposited under reduced pressure of 0.1 Pa or less to seal the openings of the continuous pores in the porous film. Next, aluminum was deposited in a strip shape with a width of 2 mm on the surface of the porous film with the openings blocked so as to be perpendicular to the ITO film in a plan view, thereby obtaining an element for evaluating electrical conductivity of Example 2-1. The area of the 2 mm×2 mm region where the ITO film and the aluminum film intersect is the element area.
[0260] [Example 2-2] A porous film with blocked openings was obtained in the same manner as in Example 2-1, except that TPBi was used instead of 2TNATA as the organic semiconductor. Next, a pressure of 10 -4 Under reduced pressure of less than 1 Pa, LiF was deposited at a deposition rate of 0.02 nm / s to a thickness of 0.8 nm. Next, an aluminum film was deposited by vapor deposition in the same manner as in Example 2-1 to obtain an element for evaluating electrical conductivity of Example 2-2.
[0261] [Example 2-3] An element for evaluating the conductivity of Example 2-3 was obtained in the same manner as in Example 2-1, except that NDP-9 (purchased from Bunseki Kobo Co., Ltd.) was further co-deposited at a deposition rate of 0.01 nm / s during the co-deposition of 2TNATA and fluorine-containing polymer A.
[0262] [Example 2-4] The substrate was cleaned in the same manner as in Example 2-1 and placed in a vacuum deposition machine at a pressure of 10 -4 Under reduced pressure of less than 1 Pa, 2TNATA was evaporated to obtain an organic semiconductor evaporated film with a thickness of about 100 nm. The evaporation rate was 0.1 nm / sec. On the surface of the obtained vapor-deposited film, aluminum was vapor-deposited in a strip shape having a width of 2 mm so as to be perpendicular to the ITO film in a plan view, thereby obtaining an element for evaluating electrical conductivity of Example 2-4.
[0263] [Example 2-5] An organic semiconductor film was obtained in the same manner as in Example 2-4, except that TPBi was used instead of 2TNATA as the organic semiconductor. The surface of the obtained deposition film was subjected to a pressure of 10 -4 Under reduced pressure of less than 1 Pa, LiF was deposited at a deposition rate of 0.02 nm / s to a thickness of 0.8 nm. Next, an aluminum film was deposited by vapor deposition in the same manner as in Example 2-1 to obtain an element for evaluating electrical conductivity of Example 2-5.
[0264] Among the above-mentioned Examples 2-1 to 2-5, Examples 2-1 to 2-3 correspond to Examples, and Examples 2-4 and 2-5 correspond to Comparative Examples.
[0265] Table 5 shows the results of evaluation of Examples 2-1 to 2-5 by the above-mentioned methods.
[0266] [Table 5]
[0267] The evaluation results showed that the conductivity of the porous deposited films of Examples 2-1 to 2-3 was comparable to that of the deposited films of Examples 2-4 and 2-5 that did not have internal voids.
[0268] <Evaluation 3: Optical calculation of organic EL elements> [Examples 3-1 to 3-10] In order to verify the effect of improving the light extraction efficiency by making the organic layers of an organic EL element (hole transport layer, light-emitting layer, electron transport layer) nanoporous and thereby reducing the refractive index, a simulation was performed using the method described above.
[0269] The analyzed device configuration was glass (thickness 1 mm) as the substrate, ITO (thickness 100 nm) as the anode, 2-TNATA as the first hole transport layer, α-NPD as the second hole transport layer, a layer (thickness 15 nm) containing Ir(ppy)3 as the emitting guest and 4,4'-bis(9H-carbazol-9-yl)biphenyl (CBP) as the emitting host as the emitting layer, TPBi as the electron transport layer, and Al (thickness 100 nm) as the cathode.
[0270] For the simulation, the wavelength of the Default Optics Settings was set to 550 nm. The materials that make up each layer are ITO, 2-TNATA, α-NPD, and Ir(ppy). 3The optical data for Al was taken from the optical data (refractive index, extinction coefficient) in Setfos4.6.11. The optical data of TPBi was measured using multi-angle spectroscopic ellipsometry (refractive index 1.75 at wavelength 550 nm, extinction coefficient 1×10 -5 ) was used.
[0271] The light-emitting layer was set as follows: Unit: probability Distribution:Dlsta Position: 0.5 Dipole orientation: Isotropic
[0272] The film thickness of the electron transport layer and the film thickness of the first hole transport layer were swept in the range of 10 to 100 nm at intervals of 10 nm, and the condition at which the light extraction efficiency was maximized was calculated.
[0273] For Examples 3-1 to 3-10, the film thicknesses of the first hole transport layer, the second hole transport layer, the light emitting layer, and the electron transport layer were set as shown in Table 6 below. In addition, whether or not a porous film was used was set for the first hole transport layer, the light emitting layer, and the electron transport layer. When a porous film was used in each example, "O" was indicated in the porous film column in Table 6.
[0274] [Table 6]
[0275] When the first hole transport layer is a porous film, the refractive index at a wavelength of 550 nm is 1.45 and the extinction coefficient is 4.8 × 10 -9 It was decided that this was the case. When the light-emitting layer is a porous film, the refractive index at a wavelength of 550 nm is 1.45 and the extinction coefficient is 4.8 × 10 -9 It was decided that this was the case. When the electron transport layer is a porous film, the refractive index at a wavelength of 550 nm is 1.39 and the extinction coefficient is 2.0 × 10 -7 It was decided that this was the case.
[0276] Among the above-mentioned Examples 3-1 to 3-10, Examples 3-1 to 3-9 correspond to Examples, and Example 3-10 corresponds to a Comparative Example.
[0277] The evaluation results are shown in Table 7 below.
[0278] [Table 7]
[0279] As a result of the evaluation, it was found that Examples 3-1 to 3-9 in which at least one of the hole transport layer, the light emitting layer, and the electron transport layer was a porous film had higher light extraction efficiency than Example 3-10 which did not have a porous film.
[0280] From the above results, it was confirmed that the present invention is useful. The entire contents of the specification, claims, abstract and drawings of Japanese Patent Application No. 2019-194241, filed on October 25, 2019, are hereby incorporated by reference as the disclosure of the specification of the present invention. [Explanation of symbols]
[0281] 1 to 3...Porous film, 10, 20...Co-deposited film, 11, 13...Continuous hole, 11a...Opening, 50...Substrate, 60...Fluorine-containing solvent, 51, 52...Vapor deposition source, 51a, 53a, 55a...Organic semiconductor, 51b, 53b...(Organic semiconductor) domain, 52a, 54a...Fluorine-containing polymer, 52b, 54b...(Fluorine-containing polymer) domain, 100, 200...Organic EL element (organic photoelectron element), 110, 210...Substrate, 111...Anode, 112...Hole injection layer, 113...Hole transport layer, 114...Emitting layer, 115...Electron transport layer, 116...Electron injection layer, 117, 217...Cathode, 500...Chamber, 600...Reservoir
Claims
1. a deposition step of co-depositing a fluorine-containing polymer soluble in a fluorine-containing solvent and an organic semiconductor to form a film; A removing step of removing the fluorine-containing polymer contained in the film from the film, In the vapor deposition step, the ratio of the fluorine-containing polymer to the total of the fluorine-containing polymer and the organic semiconductor is 20 to 80% by volume, in the removing step, a fluorine-containing solvent that dissolves the fluorine-containing polymer but does not substantially dissolve the organic semiconductor is used to dissolve the fluorine-containing polymer contained in the film in the fluorine-containing solvent and remove the fluorine-containing polymer, thereby forming a plurality of continuous pores extending in a thickness direction of the film. A method for manufacturing a porous membrane.
2. The method for producing a porous film according to claim 1, wherein the organic semiconductor has a molecular weight of 300 to 1000.
3. The method for producing a porous film according to claim 1 or 2, wherein in the vapor deposition step, a dopant for the organic semiconductor is co-deposited together with the fluorine-containing polymer and the organic semiconductor.
4. The method for producing a porous membrane according to any one of claims 1 to 3, wherein the weight average molecular weight of the fluorine-containing polymer is 1,500 to 50,000.
5. The method for producing a porous membrane according to any one of claims 1 to 4, wherein the fluorine-containing polymer has a threshold temperature of 340°C or less as determined under the following conditions: (Measurement conditions) Fluorine-containing polymer 1×10 -3 When heated at a vacuum of 100 Pa at a temperature increase of 2°C per minute, the evaporation rate was 0.1 g / (m 2 ·sec) to 0.1 g / (m 2 The boundary temperature at which the temperature is equal to or higher than the threshold temperature (seconds).
6. The method for producing a porous membrane according to any one of claims 1 to 5, wherein the fluorine-containing polymer is a perfluoropolymer having an aliphatic ring structure in the main chain.
7. The method for producing a porous membrane according to any one of claims 1 to 5, wherein the fluorine-containing polymer is a polymer having no aliphatic ring structure in its main chain and having a perfluoroalkyl group in its side chain.
8. The fluorine-containing solvent's fluorinophilicity parameter P is determined by the following method: F The method for producing a porous membrane according to any one of claims 1 to 7, wherein is 1 or more. (Fluorophilic parameter P F ) 30 μL of the fluorine-containing solvent is dropped into a two-phase system of 3 g of toluene and 3 g of perfluoromethylcyclohexane, mixed, and allowed to stand overnight, and then the fluorine-containing solvent contained in the toluene and the fluorine-containing solvent contained in the perfluoromethylcyclohexane are measured by gas chromatography. The concentration of the fluorine-containing solvent in the toluene (unit: mL / L) is P The concentration of the fluorine-containing solvent in the perfluoromethylcyclohexane (unit: mL / L) is M F In this case, the value obtained by the following formula (A) is defined as the fluorine-containing parameter PF. P F =M F / M P …(A)
9. The method for producing a porous membrane according to any one of claims 1 to 8, wherein in the removing step, the membrane is immersed in the fluorine-containing solvent.
10. The method for producing a porous membrane according to any one of claims 1 to 8, wherein in the removing step, the membrane is exposed to vapor of the fluorine-containing solvent.
11. Using a plurality of the organic semiconductors, in the vapor deposition step, a first film is formed by co-depositing the fluorine-containing polymer and a first organic semiconductor, and then a second film is formed by co-depositing the fluorine-containing polymer and a second organic semiconductor; The method for producing a porous membrane according to any one of claims 1 to 10, wherein in the removing step, the fluoropolymer contained in the first membrane and the fluoropolymer contained in the second membrane are removed.
12. The method for producing a porous film according to any one of claims 1 to 11, further comprising, after the removing step, a step of depositing the organic semiconductor to close openings of the plurality of continuous pores.
Citation Information
Patent Citations
New polymer complex and electroluminescent element using the same
JP2001106782A
Electronic devices containing organic semiconductors
JP2007536718A
Porous membrane for light-emitting devices
JP2014508385A
Organic optoelectric element
WO2019039564A1